Crystallizable shrinkable films and thermoformable sheets made from resin blends

A blend of specific polyesters with diol monomers in shrink films and sheets addresses the challenges of controlled shrinkage, toughness, and recyclability, ensuring they do not interfere with PET recycling, thereby improving recycling efficiency.

CN119192795APending Publication Date: 2024-12-27EASTMAN CHEM CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411325143.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-04-06
Filing Date
2021-04-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing shrink films and thermoformable sheets face challenges in achieving low onset shrinkage temperature, controlled shrinkage, sufficient shrink force, high ultimate shrinkage, low shrinkage in orthogonal directions, film toughness, and recyclability, while also not interfering with PET recycling processes.

Method used

A blend of polyesters containing specific diol monomers, such as terephthalic acid, neopentyl glycol, 1,4-cyclohexanedimethanol, ethylene glycol, and diethylene glycol, is used to create crystallizable films and sheets that are amorphous but have high strain-induced crystalline melting points, allowing them to be recycled with PET without forming lumps and affecting the process.

Benefits of technology

The films and sheets exhibit excellent shrink film properties, including controlled shrinkage and toughness, while being recyclable without interfering with PET recycling, thus enhancing the efficiency and yield of the recycling process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192795A_ABST
    Figure CN119192795A_ABST
Patent Text Reader

Abstract

The invention discloses a crystallizable shrinkable film and a thermoformable sheet made from a resin blend. The present disclosure relates to crystallizable, shrinkable films and thermoformable one or more films or one or more sheets comprising a blend of a polyester composition comprising terephthalic acid residues, neopentyl glycol (NPG) residues, 1, 4-cyclohexanedimethanol (CHDM) residues, ethylene glycol (EG) residues, diethylene glycol (DEG) residues, and / or 2, 2, 4, 4-tetramethyl-1, 3-pentanediol residues in a range of compositions. The present invention relates to polyester compositions comprising 1, 2, 4, 4-tetramethyl-1, 3-butanediol (TMCD) residues, which have certain advantages and improved properties.
Need to check novelty before this filing date? Find Prior Art

Description

This application is a divisional application of the invention application with application number "202180040798.0" and invention name "Crystallizable shrinkable film and thermoformable sheet made of resin blend". Technical Field

[0001] The present disclosure relates to crystallizable shrinkable films and thermoformable sheets comprising a blend of polyester compositions comprising terephthalic acid residues, neopentyl glycol (NPG) residues, 1,4-cyclohexanedimethanol (CHDM) residues, ethylene glycol (EG) residues, diethylene glycol (DEG) residues and / or 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues within a certain composition range, the polyester compositions having certain advantages and improved properties. Background Art There is a commercial need for shrink films having at least one of the following desirable shrink film properties: (1) a low onset shrinkage temperature, (2) a shrinkage percentage that increases gradually (and in a controlled manner) with increasing temperature over the temperature range in which shrinkage occurs, (3) a shrink force that is sufficiently low to prevent crushing of an underlying container, (4) a high ultimate shrinkage (shrinkage at maximum temperature), such as a shrinkage of 50% or greater in the principal shrink direction at 95°C, (5) low shrinkage in a direction orthogonal to the direction of high shrinkage, (6) improved film toughness to prevent unwanted rupture, breakage, tearing, splitting, blistering or wrinkling of the film during manufacturing and before and after shrinkage, and (7) recyclability.

[0003] There is a commercial need for thermoformable sheets having good properties and recyclability. Summary of the invention It has been found that blends made of polyesters containing certain combinations of diol monomers in shrink film resin compositions can produce films with good shrink film properties, and the mold is also crystallizable, so that it does not affect the recovery of the accompanying PET flakes during recycling. These crystallizable shrink film resin blends can be processed with PET bottles and ultimately as a component in the recyclable PET flakes that leave the recycling process. It has also been found that in blends containing certain diol monomers, the selection and quantity of a specific combination of polyesters are important for preparing films with good shrink film properties and preparing crystallizable films. The optimized polyester resin blend compositions disclosed herein are amorphous but crystallizable. Therefore, they show good properties in film applications including as shrink films, but they have high strain-induced crystalline melting points, so they provide excellent performance in the recycling process. The shrink film labels disclosed herein do not have to be removed during the recycling process, and they do not affect the process.

[0005] Heat shrinkable films must meet various adaptability requirements for the use standards implemented in this application. The film must be tough, must shrink in a controlled manner, and must provide sufficient shrinkage force to hold itself on the bottle without crushing the contents. In addition, polyester shrink film labels must not interfere with the recycling process of the bottles when these labels are applied to polyester containers. It would be advantageous if the label could be recyclable so that the entire bottle, including the label, could be recycled and converted into a new product without incurring additional disposal requirements or creating new environmental issues. Heat shrinkable films have been prepared from a variety of raw materials to meet a range of material requirements. The present disclosure describes unique and unexpected effects measured with blends of polyesters made from certain monomer combinations for shrink film resin compositions.

[0006] Polyester shrink film compositions have been used commercially as shrink film labels for food, beverages, personal care, household items, and the like. Typically, these shrink films are used in combination with clear polyethylene terephthalate (PET) bottles or containers. The entire package (bottle plus label) is then placed in the recycling process. At a typical recycling center, the PET and shrink film materials can end up together at the end of the process due to the similarity in composition and density. The PET flakes need to be dried to remove residual water that remains with the PET during the recycling process. Typically, PET is dried at temperatures above 200°C. At these temperatures, typical polyester shrink film resins will soften and become sticky, often creating lumps with the PET flakes. These lumps must be removed before further processing. These lumps reduce the yield of PET flakes from the process and create additional processing steps.

[0007] Furthermore, it has been discovered that certain combinations of diol monomers in a film or sheet resin composition can produce films or sheets with good performance properties and that are also crystallizable so that they do not affect the recycling of PET flakes. These crystallizable film or sheet resins can be processed with recycled PET and end up as a component in the recyclable PET flakes that exit the recycling process. It has also been discovered that the selection and amount of a particular combination of diol monomers is important for making films or sheets with good performance properties and for making films or sheets that are crystallizable; in other words, the polyester composition is amorphous but is "crystallizable" in the sense that it has a high strain-induced crystalline melting point. Thus, they exhibit good properties in film or sheet applications, including molded, thermoformed or formed parts and / or articles, but they also have a high strain-induced crystalline melting point, so they can be recycled with PET because when recycled PET flakes are subjected to high temperature drying conditions, the crystallizable polyesters of the present invention do not form lumps, which interfere with the normal mechanical operation of sheeting, drying of the flakes, and feeding the flakes into an extruder for further processing into (recycled) polyester pellets. Similarly, the sheets of the present disclosure do not have to be removed during the recycling process because they do not adversely affect the recycling process. (See, e.g., https: / / www.thebalancesmb.com / recycling-polyethylene-terephthalate-pet-2877869.) One embodiment of the present disclosure is a crystallizable film comprising a blend of polyester compositions comprising: (1) at least one crystallizable polyester comprising: residues of terephthalic acid, neopentyl glycol (NPG), 1,4-cyclohexanedimethanol (CHDM), ethylene glycol (EG), and diethylene glycol (DEG) within a certain composition range, and (2) at least one amorphous polyester comprising: residues of terephthalic acid, neopentyl glycol (NPG), 1,4-cyclohexanedimethanol (CHDM), ethylene glycol (EG), and diethylene glycol (DEG) within a certain composition range.

[0008] One embodiment of the present disclosure is directed to a crystallizable polyester blend composition.In one embodiment, the crystallizable polyester blend composition comprises: (a) 5-95 wt% of a crystallizable polyester composition and (b) 5-95 wt% of at least one amorphous polyester composition.

[0009] One embodiment of the present disclosure is a crystallizable composition comprising a blend of polyester compositions comprising: (1) 5 to 80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and A diol component selected from (b) or (b'), wherein (b) is a diol component comprising: about 75 mole % or more of ethylene glycol residues, and About 25 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 25 mole % neopentyl glycol residues; (ii) from about 0 to less than about 25 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 0 mole % to less than about 10 mole % total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (b') is a diol component comprising: about 75 mole % or more of ethylene glycol residues, and About 25 mole % or less of other diols comprising one or more of: (i) from about 0.1 to less than about 24 mole percent neopentyl glycol residues; (ii) from about 0.1 to less than about 24 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 1 to less than about 10 mole percent of the total diethylene glycol residues in the final polyester composition; The total mol % of the dicarboxylic acid components is 100 mol %, and the total mol % of the diol components is 100 mol %.

[0010] as well as (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 60 mole % or more of ethylene glycol residues, and About 40 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 40 mole % neopentyl glycol residues; (ii) from about 0 to less than about 40 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 15 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0011] One embodiment of the present disclosure is a crystallizable composition comprising a blend of polyester compositions comprising: (1) 5 to 80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 80 mole % or more of ethylene glycol residues, and About 20 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 20 mole % neopentyl glycol residues; (ii) from about 0 to less than about 20 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 10 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 70 mole % or more of ethylene glycol residues, and About 30 mole % or less of other glycols comprising one or more of: (i) from about 0 to less than about 30 mole % neopentyl glycol residues; (ii) from about 0 to less than about 30 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 15 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0012] One embodiment of the present disclosure is a crystallizable composition comprising a blend of polyester compositions comprising: (1) 5 to 80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 85 mole % or more of ethylene glycol residues, and About 15 mole % or less of other glycols comprising one or more of: (i) from about 0 to less than about 15 mole % neopentyl glycol residues; (ii) from about 0 to less than about 15 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 5 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and (2) 20 to 95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 60 mole % or more of ethylene glycol residues, and About 40 mole % or less of other diols comprising one or more of: (i) neopentyl glycol residues; (ii) 1,4-cyclohexanedimethanol residues; and (iii) diethylene glycol residues, whether or not formed in situ, in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0013] One embodiment of the present disclosure is a crystallizable composition comprising a blend of polyester compositions comprising: (1) 5-80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 30 mole % of neopentyl glycol residues; (ii) from about 0 to about less than 30 mole percent of 1,4-cyclohexanedimethanol residues; (iii) residues of diethylene glycol; and The remainder of the diol component comprises: (iv) a residue of ethylene glycol, and (v) optionally, 0.1 to 20 mole % of the residue of at least one modifying diol; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and (2) 20 to 95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 40 mole % neopentyl glycol residues; (ii) from about 0 to about less than 40 mole percent of 1,4-cyclohexanedimethanol residues; (iii) diethylene glycol residues, whether or not formed in situ; and The remainder of the diol component comprises: (iv) a residue of ethylene glycol, and (v) 0 to 20 mol %, or 0 to 10 mol %, or 0 to 5 mol % of the residue of at least one modifying diol; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; wherein (1) and (2) are different.

[0014] In other embodiments of the present disclosure, the blend composition has a crystalline melting point of about 200 to about 255°C.

[0015] In other embodiments of the present disclosure, the above blend has a crystalline melting point of about 220°C to about 230°C or about 245°C to about 255°C. In other embodiments, component (1) has a crystalline melting point of about 220°C to about 230°C.

[0016] One embodiment of the present disclosure is the crystallizable film of the aforementioned embodiment, wherein the film is stretched in at least one direction, and the strain-induced crystalline melting point of the stretched film is 200° C. or higher.

[0017] One embodiment of the present disclosure is a thermoformable or thermoformable film or sheet comprising a blend of polyester compositions comprising: (1) at least one crystallizable polyester comprising: residues of terephthalic acid, neopentyl glycol (NPG), 1,4-cyclohexanedimethanol (CHDM), ethylene glycol (EG), and diethylene glycol (DEG) within a certain composition range, and (2) at least one amorphous polyester comprising: residues of terephthalic acid, neopentyl glycol (NPG), 1,4-cyclohexanedimethanol (CHDM), ethylene glycol (EG), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), and diethylene glycol (DEG) within a certain composition range.

[0018] One embodiment of the present disclosure is directed to a thermoformable or thermoformable film or sheet comprising a crystallizable polyester blend composition. In one embodiment, the thermoformable or thermoformable film or sheet comprises a crystallizable polyester blend composition comprising: (a) 5-95 wt. % of a crystallizable polyester composition and (b) 5-95 wt. % of at least one amorphous polyester composition.

[0019] One embodiment of the present disclosure is a thermoformable sheet having a thickness of about 0.25 mm to about 6.4 mm, comprising a crystallizable composition comprising a blend of polyester compositions comprising: (1) 5 to 80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and A diol component selected from (b) or (b'), wherein (b) is a diol component comprising: about 75 mole % or more of ethylene glycol residues, and About 25 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 25 mole % neopentyl glycol residues; (ii) from about 0 to less than about 25 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 10 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (b') is a diol component comprising: about 75 mole % or more of ethylene glycol residues, and About 25 mole % or less of other diols comprising one or more of: (i) from about 0.1 to less than about 24 mole percent neopentyl glycol residues; (ii) from about 0.1 to less than about 24 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 1 to less than about 10 mole percent of the total diethylene glycol residues in the final polyester composition; The total mol % of the dicarboxylic acid components is 100 mol %, and the total mol % of the diol components is 100 mol %.

[0020] as well as (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 60 mole % or more of ethylene glycol residues, and About 40 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 40 mole % neopentyl glycol residues; (ii) from about 0 to less than about 40 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 15 mole % total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0021] One embodiment of the present disclosure is a thermoformable sheet having a thickness of about 0.25 mm to about 6.4 mm, comprising a crystallizable composition comprising a blend of polyester compositions comprising: (1) 5 to 80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 80 mole % or more of ethylene glycol residues, and About 20 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 20 mole % neopentyl glycol residues; (ii) from about 0 to less than about 20 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 10 mole percent of total diethylene glycol residues, whether or not formed in situ, in the final polyester composition: wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 70 mole % or more of ethylene glycol residues, and About 30 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 30 mole % neopentyl glycol residues; (ii) from about 0 to less than about 30 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 15 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0022] One embodiment of the present invention is a thermoformable sheet having a thickness of about 0.25 mm to about 6.4 mm, comprising a crystallizable composition comprising a blend of polyester compositions comprising: (1) 5 to 80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 80 mole % or more of ethylene glycol residues, and About 15 mole % or less of other glycols comprising one or more of: (i) from about 0 to less than about 15 mole % neopentyl glycol residues; (ii) from about 0 to less than about 15 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 5 mole percent of total diethylene glycol residues in the final polyester composition, wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 60 mole % or more of ethylene glycol residues, and About 40 mole % or less of other diols comprising one or more of: (i) neopentyl glycol residues; (ii) 1,4-cyclohexanedimethanol residue; (iii) total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0023] One embodiment of the present disclosure is a thermoformable sheet having a thickness of about 0.25 mm to about 6.4 mm, comprising a crystallizable composition comprising a blend of polyester compositions comprising: (1) 5-80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 30 mole % of neopentyl glycol residues; (ii) from about 0 to about less than 30 mole percent of 1,4-cyclohexanedimethanol residues; (iii) residues of diethylene glycol; and The remainder of the diol component comprises: (iv) a residue of ethylene glycol, and (v) optionally, 0.1 to 10 mole % of the residue of at least one modifying diol; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 40 mole % neopentyl glycol residues; (ii) from about 0 to about less than 40 mole percent of 1,4-cyclohexanedimethanol residues; (iii) residues of diethylene glycol; and The remainder of the diol component comprises: (iv) a residue of ethylene glycol, and (v) optionally, 0.1 to 10 mole % of the residue of at least one modifying diol; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0024] A crystallizable composition comprising a blend of polyester compositions comprising: (1) 5-80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and A diol component selected from (b) or (b'), wherein (b) is a diol component comprising: about 75 mole % or more of ethylene glycol residues, and About 25 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 25 mole % neopentyl glycol residues; (ii) from about 0 to less than about 25 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 10 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (b') is a diol component comprising: about 75 mole % or more of ethylene glycol residues, and About 25 mole % or less of other diols comprising one or more of: (i) from about 0.1 to less than about 24 mole percent neopentyl glycol residues; (ii) from about 0.1 to less than about 24 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 1 to less than about 10 mole percent of the total diethylene glycol residues in the final polyester composition; The total mol % of the dicarboxylic acid components is 100 mol %, and the total mol % of the diol components is 100 mol %.

[0025] as well as (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 60 mole % or more of ethylene glycol residues, and About 40 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 40 mole % neopentyl glycol residues; (ii) from about 0 to less than about 40 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 15 mole percent of total diethylene glycol residues in the final polyester composition, wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0026] In one embodiment, a crystallizable composition is provided, comprising a blend of polyester compositions comprising: (1) 5 to 80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 80 mole % or more of ethylene glycol residues, and About 20 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 20 mole % neopentyl glycol residues; (ii) from about 0 to less than about 20 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 10 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 70 mole % or more of ethylene glycol residues, and About 30 mole % or less of other diols comprising one or more of: (i) from about 0 to less than about 30 mole % neopentyl glycol residues; (ii) from about 0 to less than about 30 mole percent of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 15 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0027] In one embodiment, a crystallizable composition is provided, comprising a blend of polyester compositions comprising: (1) 5-80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 85 mole % or more of ethylene glycol residues, and About 15 mole % or less of other glycols comprising one or more of: (i) from about 0 to less than about 15 mole % neopentyl glycol residues; (ii) from about 0 to less than about 15 mole % of 1,4-cyclohexanedimethanol residues; (iii) from about 0 to less than about 5 mole % of total diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: about 60 mole % or more of ethylene glycol residues, and About 40 mole % or less of other diols comprising one or more of: (i) neopentyl glycol residues; (ii) 1,4-cyclohexanedimethanol residues; and (iii) diethylene glycol residues in the final polyester composition; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and wherein (1) and (2) are different.

[0028] In one embodiment, a crystallizable composition is provided, comprising a blend of polyester compositions comprising: (1) 5-80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 30 mole % of neopentyl glycol residues; (ii) from about 0 to about less than 30 mole percent of 1,4-cyclohexanedimethanol residues; (iii) diethylene glycol residues; and The remainder of the diol component comprises: (iv) a residue of ethylene glycol, and (v) optionally, 0.1 to 10 mole % of the residue of at least one modifying diol; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 40 mole % neopentyl glycol residues; (ii) from about 0 to about less than 40 mole percent of 1,4-cyclohexanedimethanol residues; (iii) diethylene glycol residues; and The remainder of the diol component comprises: (iv) a residue of ethylene glycol, and (v) optionally, or 0.1 to 10 mole % of at least one modifying diol residue; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %, and wherein (1) and (2) are different.

[0029] In one embodiment of the present invention, a crystallizable composition comprising a polyester composition blend is provided. 1) 5-80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 30 mole % of neopentyl glycol residues; (ii) from about 0 to about less than 30 mole percent of 1,4-cyclohexanedimethanol residues; (iii) diethylene glycol residues, whether or not formed in situ; and The remainder of the diol component comprises: (iv) a residue of ethylene glycol, and (v) optionally, 0 to 20 mol %, or 0 to 10 mol %, or 0 to 5 mol % of the residue of at least one modifying diol; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %, and wherein the crystalline melting point of the crystalline polyester composition is higher than 200° C.; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 40 mole %, or from about 0.01 to about 40 mole %, or from about 1 to about 40 mole % of 2,2-dimethylpropane-1,3-diol (neopentyl glycol or NPG) residues; (ii) from about 0 to about 100 mol%, or from about 0.01 to about 100 mol%, or from about 1 to about 100 mol%, or from about 55 to 99.99 mol%, or from about 25 to 40 mol%, or from about 55 to 99 mol%, or from about 60 to 85 mol% of 1,4-cyclohexanedimethanol (CHDM) residues; (iii) from about 0 to about 45 mol%, or from 0.01 to 45 mol%, or from about 1 to about 45 mol%, or from about 15 to about 40 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; (iv) from about 0 to about 40 mol %, or 0.01 to 40 mol % residues of diethylene glycol (DEG), whether or not formed in situ; The remainder of the diol component comprises: (v) optionally, ethylene glycol residues, and (vi) optionally, from about 0 to about 10 mole % of at least one other modifying glycol residue (not described in (i)-(v) above); wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %, and wherein the crystalline melting point of the amorphous polyester composition is below 170°C.

[0030] In one embodiment, the amorphous polyester of the foregoing embodiment may contain diol residues in any of the following amounts: 15 to 40 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 60 to 85 mole % 1,4-cyclohexanedimethanol; 20 to 40 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 60 to 80 mole % 1,4-cyclohexanedimethanol; 20 to 35 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 65 to 80 mole % 1,4-cyclohexanedimethanol; 20 to 30 mol % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 70 to 80 mol % 1,4-cyclohexanedimethanol; 30 to 40 mol % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 60 to 70 mol % 1,4-cyclohexanedimethanol; 20 to 25 mol % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 75 to 80 mol % 1,4-cyclohexanedimethanol; and 30-35 mol % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 65-70 mol % 1,4-cyclohexanedimethanol. In one embodiment of the present invention, the polyester useful in the present invention may contain diacid residues of terephthalic acid, isophthalic acid, or mixtures thereof in an amount of 70-100 mol %, or 80-100 mol %, or 90-100 mol %.

[0031] In one embodiment, the amorphous polyester useful in the paragraphs (which are the two preceding paragraphs) may contain diol residues in an amount of 10-27 mol % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 73-90 mol % ethylene glycol; in one embodiment of the present invention, the polyester useful in the present invention may contain diacid residues in an amount of 70-100 mol %, or 80-100 mol %, or 90-100 mol % of terephthalic acid, isophthalic acid or a mixture thereof.

[0032] In one embodiment, there is provided a composition of any of the seven preceding paragraphs, wherein the blend has a crystalline melting point of from about 200 to about 255°C. In one embodiment, a composition of any of the preceding eight paragraphs is provided wherein the blend has a heat of fusion minus a heat of crystallization greater than about 8.0.

[0033] In one embodiment, there is provided the composition of any of the preceding nine paragraphs in the form of a crystallizable film.

[0034] In one embodiment, any crystallizable film of the foregoing crystallizable film embodiments is provided, wherein the film has an intrinsic viscosity of 0.50 to 0.80 dL / g as measured at 25° C. in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / dL.

[0035] In one embodiment, there is provided any crystallizable film of the foregoing crystallizable film embodiments, wherein the film has a Tg of 65°C to 80°C as measured using a TA DSC 2920 from Thermal Analyst Instrument at a scan rate of 20°C / min.

[0036] In one embodiment, any crystallizable film of the foregoing crystallizable film embodiments is provided, wherein the sum of the glycol contents of the one or more glycol monomer components capable of forming an amorphous polyester in the final polyester is 15-40 mole %, wherein the total glycol content is 100 mole %.

[0037] In one embodiment, any crystallizable film of the foregoing crystallizable film embodiments is provided, wherein the sum of the glycol contents of the one or more glycol monomer components capable of forming the amorphous polyester component in the final polyester is 20-40 mole %, wherein the total glycol content is 100 mole %.

[0038] In one embodiment, any crystallizable film of the foregoing crystallizable film embodiments is provided, wherein the sum of the glycol contents of the one or more glycol monomer components capable of forming the amorphous polyester component in the final polyester is 30-40 mole %, wherein the total glycol content is 100 mole %.

[0039] In one embodiment, there is provided any crystallizable film of the foregoing crystallizable film embodiments, wherein the film is stretched in at least one direction.

[0040] In one embodiment, there is provided any crystallizable film of the foregoing crystallizable film embodiments, wherein the film is stretched and oriented in at least one direction.

[0041] In one embodiment, any crystallizable film of the foregoing crystallizable film embodiments is provided, wherein the film is annealed.

[0042] In one embodiment, any of the foregoing crystallizable film embodiments is provided, wherein the film is annealed at a temperature of about its Tg to about 15°C above its Tg.

[0043] In one embodiment, any of the foregoing crystallizable film embodiments is provided, wherein the film is annealed at a temperature of about 75°C to about 11°C.

[0044] In one embodiment, any crystallizable film of the foregoing crystallizable film embodiments is provided, wherein the crystallizable polyester component sums the glycol content of the residues of 1,4-cyclohexanedimethanol and neopentyl glycol in the final polyester from 4 to 15 mole %, wherein the total glycol content is 100 mole %.

[0045] In one embodiment, there is provided any crystallizable film of the foregoing crystallizable film embodiments, wherein the film is stretched in at least one direction, and the stretched film has a strain-induced crystalline melting point of 200° C. or higher.

[0046] In one embodiment, there is provided any crystallizable film of the foregoing crystallizable film embodiments, wherein the film has a shrinkage in a main shrink direction of 60% or more when immersed in water at 85°C for 10 seconds.

[0047] In one embodiment, there is provided any crystallizable film of the foregoing crystallizable film embodiments, wherein when immersed in water at 85° C. for 10 seconds, the film has a shrinkage in a main shrink direction of 50% or more.

[0048] In one embodiment, there is provided any crystallizable film of the foregoing crystallizable film embodiments, wherein the film has a shrinkage in a main shrink direction of 40% or more when immersed in water at 85°C for 10 seconds.

[0049] In one embodiment, any crystallizable film of the foregoing crystallizable film embodiments is provided, wherein the film has a shrink force of 5 MPa or greater.

[0050] In one embodiment, there is provided any crystallizable film of the foregoing crystallizable film embodiments oriented in one or more directions.

[0051] In one embodiment, any crystallizable film of the aforementioned crystallizable film embodiments is provided, having a pre-oriented thickness of about 50 to 400 microns and oriented on a tenter frame at a ratio of 5:1 to 3:1 at a temperature of the film's Tg to Tg+55°C to a thickness of about 10 to about 80 microns.

[0052] In one embodiment, any crystallizable film of the aforementioned crystallizable film embodiments is provided, wherein when immersed in water at 95° C. for 10 seconds, the film shrinks by 50% to 90% in a main shrinkage direction, and the shrinkage in a direction orthogonal to the main shrinkage direction is 10% or less.

[0053] In one embodiment, a shrink film is provided comprising any crystallizable film of any of the foregoing crystallizable film embodiments.

[0054] In one embodiment, a stretched film is provided comprising any crystallizable film of any of the foregoing crystallizable film embodiments.

[0055] In one embodiment, an oriented film is provided, comprising any crystallizable film of any of the foregoing crystallizable film embodiments.

[0056] In one embodiment, a label or sleeve for application to an article, shaped article, container, plastic bottle, glass bottle, packaging, battery, hot fill container, or industrial article is provided, comprising any crystallizable film of any of the foregoing crystallizable film embodiments.

[0057] In one embodiment, an extruded or calendered film is provided comprising any crystallizable film of any of the foregoing crystallizable film embodiments.

[0058] In one embodiment, a thermoformed film or sheet is provided comprising any crystallizable film of any of the foregoing crystallizable film embodiments.

[0059] In one embodiment, a thermoformable sheet having a thickness of about 0.25 mm to about 6.4 mm is provided, comprising any crystallizable film of any of the foregoing crystallizable film embodiments.

[0060] In one embodiment, a thermoformed sheet of any of the foregoing thermoformed sheet embodiments is provided, wherein the sheet has an intrinsic viscosity of 0.50-0.80 dL / g, as measured in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / dL at 25°C.

[0061] In one embodiment, there is provided a thermoformed sheet of any of the preceding thermoformed sheet embodiments, wherein the sheet has a Tg of 65°C to 120°C as measured using a TADSC 2920 from a thermal analyzer at a scan rate of 20°C / min.

[0062] In one embodiment, a thermoformable sheet of any of the foregoing thermoformable sheet embodiments is provided wherein the sum of the glycol contents of the one or more glycol monomer components capable of forming an amorphous polyester in the final polyester is from 15 to 90 mole %, wherein the total glycol content is 100 mole %.

[0063] In one embodiment, there is provided a thermoformed sheet of any of the aforementioned thermoformed sheets, wherein the sheet is stretched in at least one direction.

[0064] In one embodiment, there is provided a thermoformed sheet of any of the preceding thermoformed sheet embodiments, wherein the sheet is stretched and oriented in at least one direction.

[0065] In one embodiment, there is provided the thermoformed sheet of any of the preceding thermoformed sheet embodiments, wherein the sheet is annealed.

[0066] In one embodiment, there is provided a thermoformed sheet of any of the preceding thermoformed sheet embodiments, wherein the sheet is annealed at a temperature of about its Tg to about 15°C above its Tg.

[0067] In one embodiment, a thermoformed sheet of any of the preceding thermoformed sheet embodiments is provided, wherein the sheet is annealed at a temperature of about 75°C to about 110°C.

[0068] In one embodiment, a thermoformable sheet of any of the foregoing thermoformable sheet embodiments is provided wherein the sum of the diol content of the crystallizable polyester component of the residues of 1,4-cyclohexanedimethanol and neopentyl glycol in the final polyester is 4 to 15 mole %, wherein the total diol content is 100 mole %.

[0069] In one embodiment, a molded or shaped article is provided, comprising or prepared from any of the thermoformed sheet of the aforementioned thermoformed sheet embodiments.

[0070] In one embodiment, medical device packaging, medical packaging, healthcare product packaging, commercial food service products, trays, containers, food trays, drums, storage boxes, bottles, food processors, blenders and mixing bowls, utensils, water bottles, crisper trays, washing machine parts, refrigerator parts, vacuum cleaner parts, ophthalmic lenses and frames or toys are provided, which contain any thermoformed sheet of the aforementioned thermoformed sheet embodiments or are prepared from any thermoformed sheet of the aforementioned thermoformed sheet embodiments.

[0071] In one embodiment, a polyester recycle stream is provided, comprising recycled poly(ethylene terephthalate) flakes having mixed therewith at least about 0.1 weight percent of at least one recycled crystallizable composition, the crystallizable composition being as defined in any of the blends or compositions of any of the foregoing blend or composition embodiments.

[0072] In one embodiment, a polyester recycled stream of any polyester recycled stream embodiment described herein is provided, wherein the stream passes the "Critical Guidance Protocol for Clear PET Articles with Labels and Closures", dated April 11, 2019, File No. PET-CG-02.

[0073] One embodiment of the present disclosure is an extruded or calendered film comprising a blend of the crystallizable composition of any of the preceding embodiments.

[0074] One embodiment of the present disclosure is a molded, thermoformed or formed article comprising or prepared from the sheet of any of the preceding embodiments.

[0075] One embodiment of the present disclosure is a medical device package, a medical package, a health care product package, a commercial food service product, a tray, a container, a food tray, a tumbler, a storage box, a bottle, a food processor, a blender and mixing bowl, a utensil, a water bottle, a crisper tray, a washing machine component, a refrigerator component, a vacuum cleaner component, an ophthalmic lens and frame, or a toy comprising or made from the thermoformed or thermoformable sheet of any of the preceding embodiments.

[0076] One embodiment of the present disclosure is a thermoformed or thermoformable sheet or an article made therefrom comprising any of the preceding claims.

[0077] One embodiment of the present disclosure is a method for preparing a thermoformed film or sheet of any of the preceding embodiments, comprising: A. heating a polyester film or sheet; B. applying air pressure, vacuum and / or physical pressure to the heated softened film or sheet; C. conforming the sheet to the shape of a mold by vacuum or pressure; D. cooling the thermoformed part and E. removing the thermoformed part or article from the mold.

[0078] The Association for Plastic Recyclers (APR) has established a test to measure whether a material is compatible with current recycling processes (PET-CG-02). In this test, labels (minimum 3% by weight) and bottles are ground to "1 / 4" to "1 / 2" flake size. The bottle flakes are then blended with unlabeled control bottle flakes at 50:50. The sample is then elutriated on a device that allows no more than 1.2% of the PET to be carried by the label. The flakes are washed at 88°C for 15 minutes with 0.3% Triton X-100 and 1.0% caustic. The flakes are then washed with water after removing all floating material, and then filtered to remove excess water. The flakes are elutriated again as before. Then for each wash sampling, 2 pounds of washed flakes are placed in a Teflon-lined baking tray and the flakes are added to a layer thickness of 1.5 inches. The tray containing the flakes is placed in a circulating oven at 208°C for 1-1 / 2 hours. The flakes are cooled and then passed through a screen with 0.0625 inch mesh openings. As the material passes through the screen, there should be no lumps of material and thus become too large to pass through the screen. This test is followed by extrusion / granulation and molding steps to ensure the quality of the flakes.

[0079] Thus, the crystallizable blend compositions of the present disclosure are advantageous components of PET recycling streams, provided that such compositions can coexist with PET in the recycling stream without the need for additional separation steps. Thus, in one embodiment of the present disclosure, a polyester recycling stream is provided, comprising recycled poly(ethylene terephthalate) flakes having at least about 0.1% by weight of the crystallizable blend of the present disclosure mixed therewith. In another embodiment, the stream is passed through "Critical Guidance Protocol for Clear PET Articles with Labels and Closures", dated April 11, 2019, File No. PET-CG-02. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 is a graph of crystallinity vs. % PET agglomeration for blends made with Resin #1 and Resin #2.

[0081] Figure 2is a graph of crystallinity vs. % PET agglomeration for blends made with Resin #2 and Resin #3. Specific implementation plan

[0082] By referring to the following detailed description of some embodiments of the present disclosure and working examples, the present disclosure can be more easily understood. According to one or more purposes of the present disclosure, some embodiments of the present disclosure are described in the Summary of the Invention and are further described below. In addition, other embodiments of the present disclosure are described herein.

[0083] Heat shrinkable plastic films are used as covers to hold objects together and as outer wraps for bottles, cans, and other types of containers. For example, such films are used to cover the cap, neck, shoulder, or ridge of a bottle, or the entire bottle; to label, protect, wrap, or add value to a product; and for other reasons. In addition, such films can be used as covers to pack objects such as boxes, bottles, boards, bars, or notebooks together in groups, and such films can also be tightly attached as wraps. The above uses take advantage of the shrinkage and internal shrinkage stress of the film.

[0084] Historically, poly(vinyl chloride) (PVC) films have dominated the shrink film market. However, polyester films have become an important alternative because polyester films do not have the environmental issues associated with PVC films. Polyester shrink films ideally have properties very similar to PVC films so that polyester can be used as a "drop-in" film replacement that can be processed in existing shrink tunnel equipment. Desirable PVC film properties for replication include the following: (1) a relatively low shrink initiation temperature, (2) a total shrinkage that increases gradually (and in a controlled manner) with increasing temperature, (3) a low shrink force to prevent crushing of the underlying container, (4) a high total shrinkage (e.g., 50% or greater), and (5) inherent film toughness to prevent unnecessary tearing and splitting of the film before and after shrinkage.

[0085] Heat shrinkable films must meet various suitability criteria for use in order to be implemented in this application. The film must be tough, must shrink in a controlled manner, and must provide sufficient shrinkage force to hold itself on the bottle without crushing the contents. In addition, when these labels are applied to polyester containers, they must not interfere with the recycling process of the PET bottles. In fact, it would be advantageous if the label was also recyclable so that the entire bottle could be recycled and converted into a new product without incurring additional disposal requirements or creating new environmental problems. Heat shrinkable films have been prepared from a variety of raw materials to meet a range of material requirements. The present disclosure describes a unique and unexpected effect, measured with a blend of polyesters containing certain monomer combinations, which improves the recyclability of polyester shrink film labels.

[0086] Shrink film compositions are used commercially as shrink film labels for food, beverages, personal care, household items, and the like. Typically, these shrink films are used in conjunction with clear polyethylene terephthalate (PET) bottles or containers. The entire package (bottle plus label) is then placed in the recycling process. At a typical recycling center, the PET and shrink film materials can end up together at the end of the process due to the similarity in composition and density. The PET flakes need to be dried to remove residual water that remains with the PET during the recycling process. Typically, PET is dried at temperatures above 200°C. At these temperatures, typical polyester shrink film resins will soften and become sticky, often creating lumps with the PET flakes. These lumps must be removed prior to further processing. These lumps reduce the yield of PET flakes from the process and create additional processing steps.

[0087] It has been found that polyesters containing certain combinations of diol monomers in shrink film polyester resin blend compositions can produce films with good shrink film properties and can also be crystallizable so that they do not affect the recovery of PET flakes during recycling. These crystallizable shrink film resin blends can be processed with PET bottles and end up as a component in recyclable PET flakes leaving the recycling process. It has also been found that the selection and amount of a specific combination of diol monomers in each composition (amorphous composition and crystallizable composition) of the crystallizable polyester blend composition is important for preparing films with good shrink film properties and preparing crystallizable films.

[0088] The term "polyester" as used herein is intended to include "copolyesters" and is understood to refer to a synthetic polymer prepared by the reaction of one or more difunctional carboxylic acids and / or polyfunctional carboxylic acids with one or more difunctional hydroxyl compounds and / or polyfunctional hydroxyl compounds, such as branching agents. Typically, the difunctional carboxylic acid can be a dicarboxylic acid, and the difunctional hydroxyl compound can be a dihydric alcohol, such as a diol and a diol. The term "diol" as used herein includes, but is not limited to, diols, diols and / or polyfunctional hydroxyl compounds, such as branching agents. Alternatively, the difunctional carboxylic acid can be a hydroxycarboxylic acid, such as p-hydroxybenzoic acid, and the difunctional hydroxyl compound can have an aromatic core with 2 hydroxyl substituents, such as hydroquinone. The term "residue" as used herein refers to any organic structure introduced into a polymer by a corresponding monomer through a polycondensation and / or esterification reaction. As used herein, the term "repeat unit" refers to an organic structure having a dicarboxylic acid residue and a diol residue bonded by an ester group. Thus, for example, a dicarboxylic acid residue can be derived from a dicarboxylic acid monomer or its associated acyl halide, ester, salt, anhydride and / or a mixture thereof. In addition, as used herein, the term "diacid" includes multifunctional acids, such as branching agents. Therefore, the term "dicarboxylic acid" as used herein is intended to include dicarboxylic acids and any derivatives of dicarboxylic acids, including their related acyl halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides and / or mixtures thereof, which can be used in the reaction process with diols to prepare polyesters. As used herein, the term "terephthalic acid" is intended to include terephthalic acid itself and its residues and any derivatives of terephthalic acid, including their related acyl halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides and / or mixtures thereof or their residues, which can be used in the reaction process with diols to prepare polyesters.

[0089] The polyester used in the present disclosure can generally be prepared from dicarboxylic acids and diols, which react in substantially equal proportions and are introduced into the polyester polymer in the form of their corresponding residues. Therefore, the polyester of the present disclosure can contain substantially equal molar proportions of acid residues (100 mole %) and diol (and / or multifunctional hydroxy compound) residues (100 mole %), so that the total mole number of repeating units is equal to 100 mole %. Therefore, the mole percentage provided in the present disclosure can be based on the total mole number of acid residues, the total mole number of diol residues, or the total mole number of repeating units. For example, based on the total acid residues, a polyester containing 10 mole % of isophthalic acid means that the polyester contains 10 mole % of isophthalic acid residues in a total of 100 mole % of acid residues. Therefore, there are 10 moles of isophthalic acid residues in every 100 moles of acid residues. In another example, a polyester containing 25 mole % 1,4-cyclohexanedimethanol based on total glycol residues means that out of a total of 100 mole % glycol residues, the polyester contains 25 mole % 1,4-cyclohexanedimethanol residues. Thus, there are 25 moles of 1,4-cyclohexanedimethanol residues for every 100 moles of glycol residues.

[0090] In certain embodiments, terephthalic acid or its esters, such as dimethyl terephthalate or a mixture of terephthalic acid residues and their esters may constitute part or all of the dicarboxylic acid component used to form the polyesters that can be used in the present disclosure. In certain embodiments, terephthalic acid residues may constitute part or all of the dicarboxylic acid component used to form the polyesters that can be used in the present disclosure. For the purposes of the present disclosure, the terms "terephthalic acid" and "dimethyl terephthalate" are used interchangeably herein. In one embodiment, dimethyl terephthalate is part or all of the dicarboxylic acid component used to prepare the polyesters that can be used in the present disclosure. In embodiments, a range of 70 to 100 mol %; or 80 to 100 mol %; or 90 to 100 mol %; or 99 to 100 mol %; or 100 mol % terephthalic acid and / or dimethyl terephthalate and / or mixtures thereof may be used.

[0091] In addition to terephthalic acid, the dicarboxylic acid component of the polyester that can be used for the present disclosure can include up to 30 mol%, up to 20 mol%, up to 10 mol%, up to 5 mol% or up to 1 mol% of one or more modified aromatic dicarboxylic acids. Another embodiment contains 0 mol% modified aromatic dicarboxylic acid. Therefore, if present, it is expected that the amount of one or more modified aromatic dicarboxylic acids can be in any range of these aforementioned endpoint values, including, for example, 0.01-10 mol%, 0.01-5 mol% and 0.01-1 mol%. In one embodiment, the modified aromatic dicarboxylic acids that can be used for the present disclosure include, but are not limited to, those with up to 20 carbon atoms, and they can be linear, para-oriented or symmetrical. Examples of modified aromatic dicarboxylic acids that can be used for the present disclosure include, but are not limited to, isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 1,4-, 1,5-, 2,6-, 2,7-naphthalene dicarboxylic acid and trans-4,4'-stilbene dicarboxylic acid and esters thereof. In one embodiment, the modifying aromatic dicarboxylic acid is isophthalic acid.

[0092] The carboxylic acid component that can be used for polyester of the present disclosure can be further modified with up to 10 mol %, for example up to 5 mol % or up to 1 mol % of one or more aliphatic dicarboxylic acids containing 2-16 carbon atoms, for example cyclohexanedicarboxylic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and / or dodecanedioic acid. Some embodiments can also include 0.01 to 10 mol %, for example 0.1 to 10 mol %, 1 or 10 mol %, 5 to 10 mol % of one or more modified aliphatic dicarboxylic acids. Another embodiment contains 0 mol % of modified aliphatic dicarboxylic acids. The total mole % of dicarboxylic acid component is 100 mol %. In one embodiment, adipic acid and / or glutaric acid are provided in the modified aliphatic dicarboxylic acid component of polyester, and can be used for the present disclosure.

[0093] The ester of terephthalic acid and other modified dicarboxylic acids or their corresponding ester and / or salt can replace dicarboxylic acid and use. Suitable examples of dicarboxylic acid esters include but are not limited to dimethyl ester, diethyl ester, dipropyl ester, diisopropyl ester, dibutyl ester and diphenyl ester. In one embodiment, ester is selected from at least one of the following: methyl ester, ethyl ester, propyl ester, isopropyl ester and phenyl ester.

[0094] In one embodiment, the diol component that can be used for the polyester composition and the polyester blend composition of the present disclosure may include 1,4-cyclohexanedimethanol. In another embodiment, the diol component that can be used for the polyester composition and the polyester blend composition of the present disclosure includes 1,4-cyclohexanedimethanol and 1,3-cyclohexanedimethanol. The molar ratio of cis / trans 1,4-cyclohexanedimethanol can vary in the range of 50 / 50 to 0 / 100, for example, 40 / 60 to 20 / 80.

[0095] The diol component useful in the crystallizable polyester composition and the crystallizable polyester blend composition of the present disclosure may include, but is not limited to, a composition wherein the sum of the residues of 1,4-cyclohexanedimethanol and the residues of neopentyl glycol in the final polyester composition is 1 to 30 mol%, or 1 to 25 mol%, 1 to 20 mol%, or 1 to 15 mol%, or 1 to 10 mol%, or 2 to 30 mol%, or 2 to 25 mol%, or 2 to 20 mol%, or 2 to 15 mol%, or 2 to 10 mol%, or 3 to 30 mol%, or 3 to 25 mol%, or 3 to 20 mol%. %, or 3 to 15 mol%, or 3 to 10 mol%, 4 to 30 mol%, or 4 to 25 mol%, 4 to 20 mol%, or 4 to 15 mol%, or 4 to 10 mol%, 5 to 30 mol%, or 5 to 25 mol%, 5 to 20 mol%, or 5 to 15 mol%, or 5 to 10 mol%, 6 to 30 mol%, or 6 to 25 mol%, 6 to 20 mol%, or 6 to 15 mol%, or 6 to 10 mol%, 7 to 30 mol%, or 7 to 25 mol%, 7 to 20 mol%, or 7 to 15 mol%, or 7 to 10 mol%, 8 to 30 mol%, or 8 to 25 mol%, 8 to 20 mol%, or 8 to 15 mol%, or 8 to 10 mol%, 9 to 30 mol%, or 9 to 25 mol%, 9 to 20 mol%, or 9 to 15 mol%, or 9 to 10 mol%, 10 to 30 mol%, or 10 to 25 mol%, 10 to 20 mol%, or 10 to 15 mol%, or 11 to 30 mol%, 11 to 30 mol%, or 11 to 25 mol%, 11 to 20 mol%, or 11 to 15 mol%, or 12 to 30 mol%, 12 to 25 mol%, or 12 to 20 mol%. %, 12 to 15 mol%, or 13 to 30 mol%, or 13 to 25 mol%, 13 to 20 mol%, or 13 to 15 mol%, 14 to 30 mol%, or 14 to 25 mol%, or 14 to 20 mol%, 14 to 15 mol%, or 15 to 30 mol%, 15 to 25 mol%, or 15 to 20 mol%, or 16 to 20 mol%, 18 to 20 mol%, or 10 to 18 mol%, 16 to 18 mol%, or 12 to 16 mol%, or 16 to 20 mol%, or 14 to 18 mol%, or 11 to 30 mol%, or from 13 to 30 mol%, or 14 to 30 mol%, or 10 to 29 mol%, or 11 to 29 mol%, or 12 to 29 mol%, or 13 to 29 mol%, or 14 to 29 mol%, or 15 to 29 mol%, or 10 to 28 mol%, or 11 to 28 mol%, or 12 to 28 mol%, or 13 to 28 mol%, or 14 to 28 mol%, or 15 to 28 mol%.In one embodiment, the sum of the residues of 1,4-cyclohexanedimethanol and the residues of neopentyl glycol in the final polyester composition can be 4-15 mole %, or 2-21 mole %, or 2 to less than 20 mole %, or 4-20 mole %, or 5-18 mole %, or 10-21 mole %, or 12-21 mole %, wherein the total mole % of the glycol component is 100 mole %.

[0096] In one embodiment, the diol component used in the crystallizable polyester composition and the crystallizable polyester blend composition of the present disclosure may contain 0-30 mol% neopentyl glycol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component used in the polyester composition and the polyester blend composition of the present disclosure may contain 0-25 mol% neopentyl glycol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component used in the polyester composition and the polyester blend composition of the present disclosure may contain 0-17 mol% neopentyl glycol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component used in the polyester composition and the polyester blend composition of the present disclosure may contain 5-20 mol% neopentyl glycol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component used in the polyester composition and the polyester blend composition of the present disclosure may contain 10-20 mol% neopentyl glycol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component used in the polyester composition and the polyester blend composition of the present disclosure may contain 10-15 mol% neopentyl glycol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component used in the polyester composition and the polyester blend composition of the present disclosure may contain 15-25 mol% neopentyl glycol, based on the total mol% of the diol component being 100 mol%.

[0097] In one embodiment, the diol component useful in the crystallizable polyester composition and the crystallizable polyester blend composition of the present disclosure may contain 0 to 30 mol%, or 0.01 to 30 mol%, or 0 to 20 mol%, or 0.1 to 20 mol%, or 2 to 20 mol%, or 0.01 to 15 mol%, or 0.01 to 14 mol%, or 0.01 to 13 mol%, or 0.01 to 12 mol%, or 0.01 to 11 mol%, or 0.01 to 10 mol%, or 0.01 to 9 mol%, or 0.01 to 8 mol%, or 0.01 to 7 mol%, or 0.01 %, or 0.01 to 5 mol%, or 3 to 15 mol%, or 3 to 14 mol%, or 3 to 13 mol%, or 3 to 12 mol%, or 3 to 11 mol%, or 3 to 10 mol%, or 3 to 9 mol%, or 3 to 8 mol%, or 3 to 7 mol%, or 2 to 10 mol%, or 2 to 9 mol%, or 2 to 8 mol%, or 2 to 7 mol%, or 2 mol% to 5 mol%, or 1 mol% to 7 mol%, or 1 mol% to 5 mol%, or 1 mol% to 3 mol% of 1,4-cyclohexanedimethanol residues, based on the total mole % of the diol component being 100 mol%.

[0098] In one embodiment, the diol component of the crystallizable polyester composition of the crystallizable polyester composition and the polyester blend composition of the present disclosure may contain 0-15 mol% of 1,4-cyclohexanedimethanol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component of the polyester composition of the present disclosure may contain 0.01 to less than 15 mol% of 1,4-cyclohexanedimethanol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component of the polyester composition of the present disclosure may contain 0-10 mol% of 1,4-cyclohexanedimethanol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component of the polyester composition of the present disclosure may contain 0.01 to less than 10 mol% of 1,4-cyclohexanedimethanol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component used in the polyester composition of the present disclosure may contain 0.01-5 mol% of 1,4-cyclohexanedimethanol, based on the total mol% of the diol component being 100 mol%. In one embodiment, the diol component used in the polyester composition of the present disclosure may contain 0 to less than 5 mol% of 1,4-cyclohexanedimethanol, based on the total mol% of the diol component being 100 mol%.

[0099] It should be understood that some other glycol residues may be formed in situ during processing. The total amount of diethylene glycol residues may be present in the crystallizable polyester blend composition used in the present disclosure, whether formed in situ during processing or intentionally added, or both, in any amount, such as 1 to 15 mol%, or 2 to 12 mol%, or 2 to 11 mol%, or 2 to 10 mol%, or 2 to 9 mol%, or 3 to 12 mol%, or 3 to 11 mol%, or 3 to 10 mol%, or 3 to 9 mol%, or 4 to 12 mol%, or 4 to 11 mol%, or 4 to 10 mol%, or 4 to 9 mol%, or 5 to 12 mol%, or 5 to 11 mol%, or 5 to 10 mol%, or 5 to 9 mol% of diethylene glycol residues, based on the total mol% of glycol components being 100 mol%.

[0100] In one embodiment, the total amount of diethylene glycol residues that may be present in the polyesters used in the present disclosure, whether formed in situ during processing or intentionally added, or both, may be 5 mol% or less, or 4 mol% or less, or 3.5 mol% or less, or 3.0 mol% or less, or 2.5 mol% or less, or 2.0 mol% or less, or 1.5 mol% or less, or 1.0 mol% or less, or 1 to 4 mol%, or 1 to 3 mol%, or 1 to 2 mol% of diethylene glycol residues, or 2 to 8 mol%, or 2 to 7 mol%, or 2 to 6 mol%, or 2 to 5 mol%, or 3 to 8 mol%, or 3 to 7 mol%, or 3 to 6 mol%, or 3 to 5 mol%, or in some embodiments, no intentionally added diethylene glycol residues, based on the total mole % of the diol component being 100 mol%. In certain embodiments, the polyester contains no added modifying diols. In certain embodiments, the diethylene glycol residues of the crystallizable polyester composition of the polyester blend composition may be 5 mol% or less.

[0101] In one embodiment, the glycol component of the polymer used in the crystallizable polyester blend composition of the present disclosure may contain up to 45 mol%, or up to 40 mol%, or up to 35 mol%, or up to 30 mol%, or up to 25 mol%, up to 20 mol%, or up to 19 mol%, or up to 18 mol%, or up to 17 mol%, or up to 16 mol%, or up to 15 mol%, or up to 14 mol%, or up to 13 mol%, or up to 12 mol%, or up to 11 mol%, or up to 10 mol%, or up to 9 mol%, or up to 8 mol%, or up to 7 mol%, or up to 6 mol%, or up to 5 mol%, or up to 4 mol%, or up to 3 mol%, or up to 2 mol%, or up to 1 mol%, or less of one or more modifying glycols (modifying glycols are defined as glycols that are not ethylene glycol, diethylene glycol, neopentyl glycol, or 1,4-cyclohexanedimethanol). In one embodiment, when 2,2,4,4-tetramethyl-1,3-cyclobutanediol is needed, the modified diol can be any not specified in the specific disclosure. In certain embodiments, the polyester used in the present disclosure can contain 10 mol % or less of one or more modified diols. In certain embodiments, the polyester used in the present disclosure can contain 5 mol % or less of one or more modified diols. In certain embodiments, the polyester used in the present disclosure can contain 3 mol % or less of one or more modified diols. In another embodiment, the polyester used in the present disclosure can contain 0 mol % of modified diols. However, it is expected that some other diol residues can be formed in situ, so that the amount of residues formed in situ is also an embodiment of the present disclosure.

[0102] In an embodiment, the modified diol used in the polymer of the crystallizable polyester blend composition, if used, contains 2 to 16 carbon atoms as defined herein. Examples of modified diols include, but are not limited to, 1,2-propylene glycol, 1,3-propylene glycol, isosorbide, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, p-xylene glycol, polybutylene glycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) and mixtures thereof. In one embodiment, isosorbide is a modified diol. In another embodiment, the modified diol includes, but is not limited to, at least one of 1,3-propylene glycol and 1,4-butanediol. In one embodiment, 1,3-propylene glycol and / or 1,4-butanediol can be excluded. If 1,4- or 1,3-butanediol is used, greater than 4 mol % or greater than 5 mol % can be provided in one embodiment. In one embodiment, the at least one modifying diol is 1,4-butanediol, which is present in an amount of 5 to 25 mole percent.

[0103] For all embodiments, the remainder of the diol component can comprise any amount of ethylene glycol residues, based on the total mole % of the diol component being 100 mole %. In one embodiment, the crystallizable polyester blend compositions useful in the present disclosure can contain 50 mole % or greater, or 55 mole % or greater, or 60 mole % or greater, or 65 mole % or greater, or 70 mole % or greater, or 75 mole % or greater, or 80 mole % or greater, or 85 mole % or greater, or 90 mole % or greater, or 95 mole % or greater, or 50 to 80 mole %, or 55 to 80 mole %, or 60 to 80 mole %, or 50 to 75 mole %, or 55 to 75 mole %, or 60 to 75 mole %, or 65 to 75 mole % of ethylene glycol residues, based on the total mole % of the diol component being 100 mole %.

[0104] In one embodiment, a shrink film is provided comprising a crystallizable polyester blend composition (i.e., components (1) and (2)), wherein the crystallizable polyester blend composition further comprises: 1,4-cyclohexanedimethanol residues present in an amount of 0.01 to about 10 mole %, diethylene glycol residues present in an amount of 2 to 9 mole %, neopentyl glycol residues present in an amount of 5 to 30 mole %, and ethylene glycol residues present in an amount of 60 mole % or more, based on the total mole % of the glycol components being 100 mole %.

[0105] In one embodiment, a shrink film is provided that includes a crystallizable polyester blend composition comprising: 1,4-cyclohexanedimethanol residues present in an amount of 0.01 to about 5 mole %, diethylene glycol residues present in an amount of 1 to 9 mole %, neopentyl glycol residues present in an amount of 5 to 25 mole %, and ethylene glycol residues present in an amount of 60 mole % or more, based on the total mole % of the glycol components being 100 mole %.

[0106] In one embodiment, a shrink film is provided that includes a crystallizable polyester blend composition comprising: 1,4-cyclohexanedimethanol residues present in an amount of about 10 to about 20 mole %, diethylene glycol residues present in an amount of 1 to 10 mole %, neopentyl glycol residues present in an amount of up to about 1 mole %, and ethylene glycol residues present in an amount of 60 mole % or greater, based on the total mole % of the glycol components being 100 mole %.

[0107] In one embodiment, a shrink film is provided, comprising a crystallizable polyester blend composition comprising: 1,4-cyclohexanedimethanol residues present in an amount of 2-7 mole %, diethylene glycol residues present in an amount of less than 10 mole %, neopentyl glycol residues present in an amount of 5-20 mole %, and ethylene glycol residues present in an amount greater than 60 mole %, based on the total mole % of the diol components being 100 mole %.

[0108] In one embodiment, a shrink film is provided, comprising a crystallizable polyester blend composition, the composition comprising: 1,4-cyclohexanedimethanol residues present in an amount less than 10 mol %, diethylene glycol residues present in an amount of 1-10 mol %, neopentyl glycol residues present in an amount greater than 5 mol %, ethylene glycol residues present in an amount of 60 mol % or greater, based on the total mole % of the diol components being 100 mol %.

[0109] In one embodiment, a shrink film is provided, wherein the sum of one or more diol monomer components capable of forming an amorphous polyester composition in the polyester blend composition is 20-45 mol%, or 22-45 mol%, or 20-40 mol%, or 24-40 mol%, or 30-45 mol%, or 25-45 mol%, or 25-40 mol% or 25-35 mol%, wherein the total mole % of the diol component content is 100 mol%.

[0110] In one embodiment, a shrink film is provided wherein the sum of the residues of 1,4-cyclohexanedimethanol and the residues of neopentyl glycol in the amorphous polyester composition of the polyester blend is 12-35 mol%, or 15-40 mol%, or 15-35 mol%, or 20-40 mol%, or 25-40 mol%, or 20-45 mol%, or 25-35 mol%, wherein the total mol% of the glycol component is 100 mol%.

[0111] In one embodiment of the present disclosure, a crystallizable film is provided comprising a blend of polyester compositions comprising: (1) at least one crystallizable polyester comprising: terephthalic acid residues, 0 to about 20 mol%, or 0 to about 17 mol%, or about 1 to about 20 mol%, or about 1 to about 17 mol%, or about 5 to about 20 mol% of neopentyl glycol (NPG) residues, and 0 to about 20 mol%, or 0 to about 17 mol%, or about 1 to about 20 mol%, or about 1 to about 17 mol%, or about 5 to about 20 mol% of 1,4-cyclohexanedimethanol (CHDM), and less than about 5 mol% of diethylene glycol (DEG) residues, wherein the remainder is in the form of ethylene glycol (EG) residues, and (2) at least one amorphous polyester comprising: terephthalic acid residues, and 0 to about 40 mol%, or 0 to about 30 mol%, or about 1 to about 40 mol%, or about 10 to about 20 mol%, or about 10 to about 40 mol%, or about 5 to about 30 mol% of neopentyl glycol (NPG), and 0 to about 40 mol%, or 0 to about 35 mol%, or about 1 to about 30 mol%, or about 10 to about 40 mol%, or about 20 to about 40 mol% of 1,4-cyclohexanedimethanol (CHDM), and 1 to about 15 mol%, or 2 to about 10 mol%, or about 5 to about 15 mol%, or about 5 to about 10 mol% of diethylene glycol (DEG), wherein the remainder is in the form of ethylene glycol (EG) residues.

[0112] In one embodiment of the present invention, the crystallizable composition comprises a blend of polyester compositions comprising: 1) 5-80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 30 mole % of neopentyl glycol residues; (ii) from about 0 to about less than 30 mole percent of 1,4-cyclohexanedimethanol residues; (iii) diethylene glycol residues, whether or not formed in situ; and The remainder of the diol component comprises: (iv) ethylene glycol residues, and (v) optionally, 0 to 20 mol%, or 0 to 10 mol%, or 0 to 5 mol% of at least one modifying diol residue; wherein the total mol% of the dicarboxylic acid component is 100 mol%, and wherein the total mol% of the diol component is 100 mol%, and wherein the crystalline melting point of the crystalline polyester composition is above 200°C; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 40 mole %, or from about 0.01 to about 40 mole %, or from about 1 to about 40 mole % of 2,2-dimethylpropane-1,3-diol (neopentyl glycol or NPG) residues; (ii) from about 0 to about 100 mol%, or from about 0.01 to about 100 mol%, or from about 1 to about 100 mol%, or from about 55 to 99.99 mol%, or from about 25 to 40 mol%, or from about 55 to 99 mol%, or from about 60 to 85 mol% of 1,4-cyclohexanedimethanol (CHDM) residues; (iii) from about 0 to about 45 mol%, or from 0.01 to 45 mol%, or from about 1 to about 45 mol%, or from about 15 to about 40 mol% of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; (iv) from about 0 to about 40 mol %, or 0.01 to 40 mol % diethylene glycol (DEG) residues, whether or not formed in situ; The remainder of the diol component comprises: (v) optionally, ethylene glycol residues, and (vi) optionally, from about 0 to about 10 mole % of at least one other modifying glycol residue (not described in (i)-(v) above); wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %, and wherein the crystalline melting point of the amorphous polyester composition is below 170°C.

[0113] In one embodiment, the amorphous polyester used in the present invention may contain diol residues in an amount of 15-40 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 60-85 mole % 1,4-cyclohexanedimethanol; 20 to 40 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 60 to 80 mole % 1,4-cyclohexanedimethanol; 20 to 35 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 65 to 80 mole % 1,4-cyclohexanedimethanol; 20 to 30 mole % 2 , 2,4,4-tetramethyl-1,3-cyclobutanediol and 70 to 80 mole % 1,4-cyclohexanedimethanol; 30 to 40 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 60 to 70 mole % 1,4-cyclohexanedimethanol; 20 to 25 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 75 to 80 mole % 1,4-cyclohexanedimethanol; and 30-35 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 65 to 70 mole % 1,4-cyclohexanedimethanol. In one embodiment of the present invention, the polyester used in the present invention may contain diacid residues in an amount of 70-100 mole %, or 80-100 mole %, or 90-100 mole % of terephthalic acid, isophthalic acid, or a mixture thereof.

[0114] In one embodiment, the amorphous polyester used in the present invention may contain diol residues in an amount of 10-27 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 73-90 mol % of ethylene glycol; in one embodiment of the present invention, the polyester used in the present invention may contain diacid residues in an amount of 70-100 mol %, or 80-100 mol %, or 90-100 mol % of terephthalic acid, isophthalic acid or a mixture thereof.

[0115] In some embodiments, the polyester composition according to the present disclosure may include 0 to 10 mol%, such as 0.01 to 5 mol%, 0.01 to 1 mol%, 0.05 to 5 mol%, 0.05 to 1 mol%, or 0.1 to 0.7 mol% (based on the total molar percentage of the diol or diacid residues), respectively, one or more residues of a branching monomer (also referred to herein as a branching agent) having 3 or more carboxyl substituents, hydroxyl substituents, or a combination thereof. In certain embodiments, the branching monomer or branching agent may be added before and / or during and / or after the polymerization of the polyester. In some embodiments, one or more polyesters useful in the present disclosure may therefore be linear or branched.

[0116] Examples of branching monomers include, but are not limited to, polyfunctional acids or polyfunctional alcohols, such as trimellitic acid, trimellitic anhydride, pyromellitic dianhydride, trimethylolpropane, glycerol, pentaerythritol, citric acid, tartaric acid, 3-hydroxyglutaric acid, and the like. In one embodiment, the branching monomer residues may contain 0.1 to 0.7 mole % of one or more residues selected from trimellitic anhydride, pyromellitic dianhydride, glycerol, sorbitol, 1,2,6-hexanetriol, pentaerythritol, trimethylolethane, and / or trimesic acid. The branching monomers may be added to the polyester reaction mixture or blended with the polyester in the form of a concentrate, such as described in U.S. Pat. Nos. 5,654,347 and 5,696,176, the disclosure of which is incorporated herein by reference.

[0117] The polyesters useful in the present disclosure may include at least one chain extender. Suitable chain extenders include, but are not limited to, multifunctional (including but not limited to difunctional) isocyanates, multifunctional epoxides, including, for example, epoxidized phenolic resins and phenoxy resins. In certain embodiments, the chain extender may be added at the end of the polymerization process or after the polymerization process. If added after the polymerization process, the chain extender may be introduced by compounding or by addition during a conversion process such as injection molding or extrusion.

[0118] The amount of chain extender used can vary depending upon the specific monomer composition used and the physical properties desired, but is typically from about 0.1 to about 10 mass %, such as from about 0.1 to about 5 mass %, based on the total weight of the polyester.

[0119] It is contemplated that the polyester blend compositions used in the present disclosure may have at least one intrinsic viscosity range described herein and at least one monomer range of the polyester compositions described herein, unless otherwise specified. It is also contemplated that, unless otherwise specified, the polyester blend compositions used in the present disclosure may have at least one of the Tg ranges described herein and at least one of the monomer ranges of the polyester compositions described herein. It is also contemplated that, unless otherwise specified, the polyester compositions used in the present disclosure may have at least one intrinsic viscosity range described herein, at least one Tg range described herein, and at least one monomer range of the polyester compositions described herein.

[0120] For embodiments of the present disclosure, the polyester compositions useful in the present disclosure may exhibit at least one of the following intrinsic viscosities as measured at a concentration of 0.5 g / dL in 60 / 40 (wt / wt) phenol / tetrachloroethane at 25° C.: 0.50-1.2 dL / g; 0.50-1.0 dL / g; 0.50-0.90 dL / g; 0.50-0.80 dL / g; 0.55-0.80 dL / g; 0.60-0.80 dL / g; 0.65-0.80 dL / g; 0.70-0.80 dL / g; 050-0.75 dL / g; 0.55-0.75 dL / g; or 060-075 dL / g.

[0121] The glass transition temperature (Tg) of the polyester of the polyester blend composition was measured using a TA DSC 2920 from a thermal analyzer at a scanning rate of 20°C / min. The value of the glass transition temperature was determined during the second heating.

[0122] In certain embodiments, the oriented or shrink film of the present disclosure comprises a polyester / polyester composition wherein the polyester has a Tg of 60° C. to 80° C.; 70 to 80° C.; or 65 to 80° C.; or 65-75° C. In certain embodiments, these Tg ranges can be met with or without at least one plasticizer during polymerization.

[0123] In embodiments of the present disclosure, certain oriented films and / or shrinkable films comprising the polyesters and / or polyester compositions used in the present disclosure may have a unique combination of all of the following properties: good stretchability, controlled shrinkage properties, certain toughness, certain intrinsic viscosity, certain glass transition temperature (Tg), certain strain induced crystalline melting point, certain flexural modulus, certain density, certain tensile modulus, certain surface tension, good melt viscosity, good clarity, and good color.

[0124] In one embodiment, certain polyester blend compositions useful in the present disclosure may be visually clear. The term "visually clear" is defined herein as the perceived absence of cloudiness, haziness, and / or haziness when visually inspected.

[0125] The polyester portion (amorphous composition and crystallizable composition) of the polyester blend composition used in the present disclosure can be prepared by methods known in the literature, such as by methods in homogeneous solutions, by transesterification methods in melts, and by two-phase interface methods. Suitable methods include, but are not limited to, steps of reacting one or more dicarboxylic acids with one or more diols at a temperature of 100° C. to 315° C. at a pressure of 0.1 to 760 mmHg for a time sufficient to form polyesters. See U.S. Pat. No. 3,772,405 for methods of producing polyesters, the disclosure of which is incorporated herein by reference.

[0126] The polyesters can generally be prepared by condensing a dicarboxylic acid or a dicarboxylic acid ester with a diol in the presence of a catalyst in an inert atmosphere at elevated temperatures which gradually increase during the condensation process up to a temperature of about 225° C. to 310° C. and conducting the condensation at low pressure during the latter part of the condensation as described in further detail in U.S. Pat. No. 2,720,507, which is incorporated herein by reference.

[0127] In some embodiments, during the method for making the polyester blend composition of the present disclosure, certain agents that color the polymer can be added to the melt, the melt containing a toner or a dye. In one embodiment, a bluing toner is added to the melt to reduce the b* of the resulting polyester polymer melt phase product. This bluing agent includes one or more blue inorganic and organic toners and / or dyes. In addition, one or more red toners and / or dyes can also be used to adjust the a* color. One or more organic toners can be used, such as one or more blue and red organic toners, such as those described in U.S. Patent Nos. 5,372,864 and 5,384,377 (which are incorporated herein by reference in their entirety). One or more organic toners can be fed as a premixed composition. The premixed composition can be a pure blend of red and blue compounds, or the composition can be pre-dissolved or slurried in one of the raw materials of the polyester, such as ethylene glycol.

[0128] The total amount of toner components added may depend on the amount of inherent yellow in the base polyester and the effectiveness of the toner. In one embodiment, a combined organic toner component may be used at a concentration of up to about 15 ppm and a minimum concentration of about 0.5 ppm. In one embodiment, the total amount of bluing additive may be in the range of 0.5 to 10 ppm. In one embodiment, one or more toners may be added to the esterification zone or polycondensation zone. Preferably, one or more toners are added to the early stages of the esterification zone or polycondensation zone, such as into a prepolymerization reactor, or the toner may be added during a compounding or extrusion step after polymerization.

[0129] The present disclosure also relates to polymers compounded with a crystallizable polyester composition as part of a polyester blend composition. In one embodiment, the compounded composition comprises: (a) 5 to 80 weight percent of the disclosed crystallizable polyester composition described herein; and (b) 20-95 weight percent of at least one polymer component (i.e., a component other than the blend of the present disclosure).

[0130] Suitable examples of polymer components include, but are not limited to, nylon; polyesters other than those described herein; polyamides, such as those from DuPont; Polystyrene; polystyrene copolymers; styrene acrylonitrile copolymers; acrylonitrile butadiene styrene copolymers; poly(methyl methacrylate); acrylic copolymers; poly(ether-imides), for example (poly(ether-imide) from SABIC); polyphenylene ethers, such as poly(2,6-dimethylphenylene ether) or poly(phenylene ether) / polystyrene blends, such as NORYL (blend of poly(2,6-dimethylphenylene oxide) and polystyrene resin from SABIC); polyphenylene sulfide; polyphenylene sulfide / polyphenylene sulfone; poly(ester-carbonate); polycarbonates, such as (polycarbonate from SABIC); polysulfone; polysulfone ether; and poly(ether-ketone) of aromatic dihydroxy compounds; or a mixture of any of the foregoing polymers. In one embodiment, aliphatic-aromatic polyesters may be excluded from the polyester composition used in the present disclosure. If such blending exceeds the compositional range of the present disclosure, the following polyesters (which may be blended to prepare the polyester composition of the present disclosure) may be excluded as polymer components for additional blending: polyethylene terephthalate (PET), glycol-modified PET (PETG), glycol-modified poly(cyclohexylene dimethylene terephthalate) (PCTG), poly(cyclohexylene dimethylene terephthalate) (PCT), acid-modified poly(cyclohexylene dimethylene terephthalate) (PCTA), poly(butylene terephthalate) and / or diethylene glycol-modified PET (EASTOBOND TM copolyester).

[0131] Blends can be prepared by conventional processing techniques known in the art such as melt blending or solution blending.

[0132] In embodiments, the polyester composition and the polymer blend composition may also contain 0.01-25 mass % of the total composition of commonly used additives, such as colorants, one or more toners, dyes, mold release agents, flame retardants, plasticizers, glass microspheres, nucleating agents, stabilizers, including but not limited to UV stabilizers, heat stabilizers, and / or reaction products thereof, fillers, and impact modifiers. Examples of commercially available impact modifiers include but are not limited to ethylene / propylene terpolymers, functionalized polyolefins such as those containing methyl acrylate and / or glycidyl methacrylate, styrene-based block copolymer impact modifiers, and various acrylic core / shell impact modifiers. Residues of these additives are also considered as part of the polyester composition.

[0133] Reinforcement can be added to the composition available in the present disclosure. Reinforcement can include but is not limited to carbon filaments, silicates, mica, clay, talc, titanium dioxide, wollastonite, glass flakes, glass beads and fibers, and polymer fibers and combinations thereof. In one embodiment, the reinforcing material comprises glass, such as a mixture of fiberglass filaments, glass and talc, a mixture of glass and mica, and a mixture of glass and polymer fibers.

[0134] In one embodiment, films and shrink films according to the present disclosure may contain 0.01 to 10 weight percent polyester plasticizer. In one embodiment, shrink films may contain 0.1 to 5 weight percent polyester plasticizer. Typically, shrink films may contain 90 to 99.99 weight percent copolyester. In certain embodiments, shrink films may contain 95 to 99.9 weight percent copolyester.

[0135] In one aspect, the present disclosure relates to one or more shrink films and one or more molded articles of the present disclosure, which include polyester compositions and / or polymer blends for the present disclosure. The method of molding polyester and / or blends into one or more films and / or one or more sheets is well known in the art. Examples of one or more films and / or one or more sheets for the present disclosure include, but are not limited to, one or more extruded films and / or sheets, one or more compression molded films, one or more calendered films and / or sheets, one or more solution cast films and / or sheets. In one aspect, the method of preparing films and / or sheets that can be used to produce shrink films of the present disclosure includes, but is not limited to, extrusion, compression molding, calendering, and solution casting.

[0136] In one embodiment, the polyester composition used in the present disclosure is made into a film using any method known in the art for making films from polyesters, such as solution casting, extrusion, compression molding, or calendaring.

[0137] In one embodiment, the as-formed film is then oriented in one or more directions (e.g., uniaxial and / or biaxially oriented films). Such orientation of the film can be performed by any method known in the art using standard orientation conditions. For example, the oriented film of the present disclosure can be made of a film having a thickness of about 100-400 microns, such as an extruded, cast, or calendered film, which can be oriented at a ratio of 5:1-3:1 at a temperature of Tg to Tg+55°C, for example, at a ratio of 5:1 or 3:1 at a temperature of 70°C to 125°C, and it can be oriented to a thickness of 20-80 microns. In one embodiment, the orientation of the initial as-formed film can be performed on a tenter frame according to these orientation conditions.

[0138] The shrink film of the present disclosure may have a shrink onset temperature of about 55°C to about 80°C, or about 55°C to about 75°C, or about 55°C to about 70°C, the shrink onset temperature being the temperature at which shrinkage begins to occur.

[0139] In certain embodiments, the polyester compositions useful in the present disclosure may have a density of 1.6 g / cc or less, or 1.5 g / cc or less, or 1.4 g / cc or less, or 1.1 g / cc to 1.5 g / cc, or 1.2 g / cc to 1.4 g / cc, or 1.2 g / cc to 1.35 g / cc.

[0140] In one embodiment, the density of the film is reduced by introducing many small voids or holes in the film or molded article. This method is called "voiding" and may also be referred to as "voiding" or "microvoiding". The voids are obtained by introducing about 1-about 50% by weight of small organic or inorganic particles (including glass microspheres) or "inclusions" (referred to in the art as "voiding" agents or "voiding" agents) into the matrix polymer and orienting the polymer by stretching in at least one direction. During the stretching process, small voids or voids are formed around the voiding agent. When voids are introduced into the polymer film, the resulting voided film not only has a lower density than the void-free film, but also becomes opaque and produces a paper-like surface. The surface also has the advantage of improved printability; that is, the surface can accept a lot of ink with a significantly larger capacity than the void-free film. Typical examples of voided membranes are described in U.S. Pat. Nos. 3,426,754; 3,944,699; 4,138,459; 4,582,752; 4,632,869; 4,770,931; 5,176,954; 5,435,955; 5,843,578; 6,004,664; 6,287,680; 6,500,533; 6,720,085; U.S. Patent Application Publication Nos. 2001 / 0036545; 2003 / 0068453; 2003 / 0165671; 2003 / 0170427; Japanese Patent Application Nos. 61-037827; 63-193822; 2004-181863; European Patent No. 0 581970 B1 and European patent application No. 0 214 859 A2.

[0141] In certain embodiments, the film of the original shape or extrusion original shape is oriented when stretched.Oriented film or shrinkable film of the present disclosure can be prepared by film with any thickness, depending on the desired end use.In one embodiment, the ideal condition is that wherein oriented film and / or shrinkable film can be printed with ink, for including label, can be adhered to the application of film on substrate such as paper, and / or it can be used for other application.It may be necessary to coextrude the polyester used for the present disclosure with another polymer such as PET, to prepare the film for preparing oriented film and / or shrink film of the present disclosure.An advantage of carrying out the latter is that in some embodiments, no adhesive layer may be required.

[0142] In one embodiment, the uniaxial and biaxially oriented films of the present disclosure can be prepared from films having a thickness of about 100-400 microns, such as extruded, cast or calendered films, which can be stretched in one or more directions at a ratio of 6.5:1-3:1 at a temperature of the film's Tg to Tg+55°C, and which can be stretched to a thickness of 20-80 microns. In one embodiment, the orientation of the initial extruded film can be carried out on a tenter according to these orientation conditions. The shrink film of the present disclosure can be made from the oriented film of the present disclosure.

[0143] In certain embodiments, the shrink films of the present disclosure have a gradual shrinkage with little or no wrinkling. In certain embodiments, the shrink films of the present disclosure have a shrinkage in the main shrink direction of no more than 40% per 5°C temperature increment.

[0144] In certain embodiments of the present disclosure, the shrink film of the present disclosure has a shrinkage of 10% or less, or 5% or less, or 3% or less, or 2% or less, or no shrinkage in the machine direction (i.e., the direction orthogonal to the main shrinkage direction) when immersed in water at 65°C for 10 seconds. In certain embodiments of the present disclosure, the shrink film of the present disclosure has a shrinkage in the machine direction of -5% to 10%, -5% to 5%, or -5% to 3%, or -5% to 2%, or -4% to 5%, or -3% to 5%, or -2% to 5%, or -2% to 3%, or -2% to 2%, or 0 to 2%, or no shrinkage when immersed in water at 65°C for 10 seconds. A negative machine direction shrinkage percentage here indicates machine direction growth. A positive machine direction shrinkage indicates machine direction shrinkage.

[0145] In certain embodiments of the present disclosure, the shrink film of the present disclosure has a shrinkage rate of 50% or more, or 60% or more, or 70% or more in the main shrinking direction when immersed in 95° C. water for 10 seconds.

[0146] In certain embodiments of the present disclosure, the shrink film of the present disclosure shrinks by 50% to 90% in the main shrink direction and by 10% or less, or -10% to 10% in the machine direction when immersed in 95° C. water for 10 seconds.

[0147] In one embodiment, the polyester used in the present disclosure is made into a film using any method known in the art for preparing a film from a polyester, such as solution casting, extrusion, compression molding, or calendaring. The extruded film as is (or formed as is) is then oriented in one or more directions (e.g., a uniaxially and / or biaxially oriented film). This orientation of the film can be performed using standard orientation conditions by any method known in the art. For example, the uniaxially oriented film of the present disclosure can be made of a film having a thickness of about 100 to 400 microns, such as an extruded, cast, or calendared film, which can be stretched at a temperature from the Tg of the film to Tg+55°C at a ratio of 6.5:1 to 3:1, and it can be stretched to a thickness of 20 to 80 microns. In one embodiment, the orientation of the initial extruded film can be performed on a tenter according to these orientation conditions.

[0148] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a shrink onset temperature of about 55°C to about 80°C, or about 55°C to about 75°C, or 55°C to about 70°C, the shrink onset temperature being the temperature at which shrinkage begins to occur.

[0149] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a shrink start temperature between 55°C and 70°C.

[0150] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a percent strain at break greater than 200% at a stretching speed of 500 mm / min in a direction orthogonal to the main shrinking direction according to ASTM method D882.

[0151] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a percent strain at break greater than 300% at a stretching speed of 500 mm / min in a direction orthogonal to the main shrinking direction according to ASTM method D882.

[0152] In certain embodiments of the present disclosure, the shrink films of the present disclosure may have a tensile stress at break (break stress) of 20 to 400 MPa; or 40-260 MPa; or 42 to 260 MPa; 20 to 100 MPa, as measured according to ASTM method D882.

[0153] In certain embodiments of the present disclosure, the shrink film of the present disclosure may have a shrink force of 4 to 18 MPa, or 4 to 15 MPa, as measured by ISO method 14616, depending on the stretching conditions and the desired end-use application. For example, some labels prepared for plastic bottles may have a shrink force of 4 to 8 MPa, and some labels prepared for glass bottles may have a shrink force of 10 to 14 MPa, as measured by ISO method 14616 using a shrink force tester manufactured by LabThink@80°C.

[0154] In one embodiment of the present disclosure, the polyester composition can be formed by reacting monomers by known methods for making polyesters in a composition generally referred to as a reactor grade composition.

[0155] In one embodiment of the present disclosure, the polyester composition of the present disclosure can be formed by blending polyesters, such as polyethylene terephthalate (PET), glycol-modified PET (PETG), glycol-modified poly(cyclohexylene dimethylene terephthalate) (PCTG), poly(cyclohexylene dimethylene terephthalate) (PCT), acid-modified poly(cyclohexylene dimethylene terephthalate) (PCTA), poly(butylene terephthalate) and / or diethylene glycol-modified PET (EASTOBOND TM copolyesters) to achieve the monomer range for these compositions.

[0156] In certain embodiments, the polyester composition and the polymer blend composition may also contain 0.01-25 mass % of common additives, such as colorants, one or more toners, dyes, mold release agents, flame retardants, plasticizers, glass microspheres, nucleating agents, stabilizers, including but not limited to UV stabilizers, heat stabilizers and / or their reaction products, fillers, and impact modifiers, based on the total composition. Examples of commercially available impact modifiers include but are not limited to ethylene / propylene terpolymers, functionalized polyolefins such as those containing methyl acrylate and / or glycidyl methacrylate, styrene-based block copolymer impact modifiers, and various acrylic core / shell impact modifiers. The residues of these additives are also considered as part of the polyester composition.

[0157] Reinforcement materials can be added to the polyester compositions for use in the present disclosure. Reinforcement materials may include, but are not limited to, carbon filaments, silicates, mica, clay, talc, titanium dioxide, wollastonite, glass flakes, glass beads and fibers, and polymer fibers and combinations thereof. In one embodiment, the reinforcement material comprises glass, such as fiberglass filaments, a mixture of glass and talc, a mixture of glass and mica, and a mixture of glass and polymer fibers.

[0158] Molded articles may also be made from any of the polyester compositions disclosed herein, which may consist of or contain a shrink film; or may not consist of or contain a shrink film, and are included within the scope of the present disclosure.

[0159] Typically, shrink films according to the present disclosure may contain 0.01 to 10 weight percent polyester plasticizer. In one embodiment, the shrink film may contain 0.1 to 5 weight percent polyester plasticizer. Typically, the shrink film may contain 90 to 99.99 weight percent copolyester. In certain embodiments, the shrink film may contain 95 to 99.9 weight percent copolyester.

[0160] In one embodiment, when having a pre-oriented thickness of about 100 to 400 microns and then oriented on a tenter frame at a temperature of Tg to Tg+55°C at a ratio of 6.5:1 to 3:1 to a thickness of about 20 to about 80 microns, the shrink film of the present disclosure may have one or more of the following properties: (1) when immersed in 95°C water for 10 seconds, the shrinkage in the main shrink direction or transverse direction is greater than 50% (or greater than 60%), and the shrinkage in the machine direction is 10% or less (or -10% to 10%); (2) (3) a percent strain at break greater than 200%, or 200 to 600%, or 200 to 500%, or 226 to 449%, or 250 to 455% at a stretching speed of 500 mm / min in the transverse direction or the machine direction or both directions according to ASTM method D882; (4) a shrinkage rate of no more than 40% per 5°C temperature increment; and / or (5) a strain-induced crystalline melting point greater than 190°C as measured at the first heat of a DSC scan according to ASTM. Any combination or all of these properties may be present in the shrink film of the present disclosure. The shrink film of the present disclosure may have a combination of two or more of the above shrink film properties. The shrink film of the present disclosure may have a combination of three or more of the above shrink film properties. The shrink film of the present disclosure may have a combination of four or more of the above shrink film properties. In certain embodiments, properties (1)-(2) are present. In certain embodiments, properties (1)-(5) are present. In certain embodiments, properties (1)-(3), etc. are present.

[0161] The shrinkage percentages herein are based on an initially stretched film having a thickness of about 20 to 80 microns, oriented on a tenter frame at a temperature of Tg to Tg+55°C at a ratio of 6.5:1 to 3:1, such as oriented at a temperature of 70°C to 85°C at a ratio of 5:1. In one embodiment, the shrinkage properties of the oriented film used to prepare the shrink film of the present disclosure are not adjusted by annealing the film at a temperature above its orientation temperature. In another embodiment, the shrinkage properties can be adjusted by annealing.

[0162] The shape of the film used to prepare the oriented film or shrink film of the present disclosure is not limited in any way. For example, it can be a flat film or a film that has been formed into a tube. In order to prepare the shrink film for the present disclosure, the polyester is first formed into a flat film, and then "uniaxially stretched", meaning that the polyester film is oriented in one direction. The edges of the stretched film are then bonded using a stitching solvent or a stitching adhesive to form a shrinkable tube. The film can also be "biaxially oriented", meaning that the polyester film is oriented in two different directions; for example, the film is stretched in both the machine direction and a direction different from the machine direction. Usually, but not always, the two directions are substantially perpendicular. For example, in one embodiment, the two directions are the longitudinal or machine direction ("MD") of the film (the direction in which the film is prepared on the film-making machine) and the transverse direction ("TD") of the film (the direction perpendicular to the MD of the film). The biaxially oriented film can be sequentially oriented, simultaneously oriented, or oriented by some combination of simultaneous and sequential stretching.

[0163] The film can be oriented by any conventional method, such as roller stretching, long gap stretching, tenter stretching and tubular stretching. In the case of any of these methods, continuous biaxial stretching, simultaneous biaxial stretching, uniaxial stretching or a combination of these can be performed. In the case of the above-mentioned biaxial stretching, stretching in the machine direction and the transverse direction can be performed simultaneously. In addition, stretching can be performed first in one direction, and then in the other direction to produce effective biaxial stretching. In one embodiment, the film is stretched by preheating the film to 5°C to 80°C above its glass transition temperature (Tg). In one embodiment, the film can be preheated from 10°C above its Tg to 30°C above its Tg. In one embodiment, the stretching rate is 5 to 20 inches (12.7 to 50.8cm) / second. Then, the film can be oriented, for example, in the machine direction, transverse direction or both directions, 2-6 times the original measured value. The film can be oriented as a single film layer, or it can be coextruded as a multilayer film with another polymer material or polyester such as PET (polyethylene terephthalate), and then oriented.

[0164] In one embodiment, the present disclosure includes an article or shaped article comprising a shrink film of any of the shrink film embodiments of the present disclosure. In another embodiment, the present disclosure includes an article or shaped article comprising an oriented film of any of the oriented film embodiments of the present disclosure.

[0165] In certain embodiments, the present disclosure includes, but is not limited to, shrink films applied to containers, plastic bottles, glass bottles, packaging, batteries, heat-filled containers, and / or industrial articles or other applications. In one embodiment, the present disclosure includes, but is not limited to, oriented films applied to containers, packaging, plastic bottles, glass bottles, photo substrates such as paper, batteries, heat-filled containers, and / or industrial articles or other applications.

[0166] In certain embodiments of the present disclosure, the shrink film of the present disclosure can be formed into a label or sleeve. The label or sleeve can then be applied to an article, such as a container wall, a battery, or to a sheet or film.

[0167] The oriented films or shrink films of the present disclosure can be applied to shaped articles, such as sheets, films, tubes, bottles, and are generally used in various packaging applications. For example, films and sheets made from polymers such as polyolefins, polystyrene, poly(vinyl chloride), polyesters, polylactic acid (PLA), etc. are often used to make shrinkable labels for plastic beverage or food containers. For example, the shrinkable films of the present disclosure can be used in many packaging applications, wherein the shaped articles will exhibit properties such as good printability, high opacity, higher shrinkage force, good texture, and good stiffness after the shrink film is applied.

[0168] The combination of improved shrink properties and improved toughness should provide new commercial options including, but not limited to, shrink films for containers, plastic bottles, glass bottles, packaging, batteries, hot fill containers and / or industrial articles or other applications.

[0169] In one aspect of the present disclosure, the disclosed polyester blend compositions can be used as one or more films or one or more sheets that are thermoformed and / or thermoformable. The present disclosure also relates to articles incorporating one or more films and / or one or more sheets of the thermoformed of the present disclosure. In one embodiment, the polyester blend compositions of the present disclosure can be used as films and sheets that are easily formed into shaped or molded articles. In one embodiment, one or more films and / or one or more sheets of the present disclosure can be processed into molded articles or parts by thermoforming. The polyester compositions of the present disclosure can be used for various molding and extrusion applications.

[0170] In addition, in one embodiment, the polyester composition and polyester blend composition useful for one or more thermoformed sheets of the present disclosure may also contain 0.1 to 25 weight percent of the total composition of common additives, such as colorants, slip agents, antiblocking agents, mold release agents, flame retardants, plasticizers, nucleating agents, stabilizers, including but not limited to UV stabilizers, heat stabilizers, fillers and impact modifiers.

[0171] In one embodiment, reinforcing materials may be included in one or more films or one or more sheets thermoformed comprising the polyester composition of the present disclosure. For example, suitable reinforcing materials may include carbon filaments, silicates, mica, clay, talc, titanium dioxide, wollastonite, glass flakes, glass beads and fibers, and polymer fibers and combinations thereof.

[0172] In one embodiment, the thermoformed film or sheet is a multilayer film or sheet.In one embodiment, at least one layer of the multilayer film or sheet is a foamed or foamed polymer or polyester layer.

[0173] One aspect of the present disclosure is a method of making molded or formed parts and articles using thermoforming.Any thermoforming technique or method known to those skilled in the art can be used to make the molded or formed articles of the present disclosure.

[0174] In one embodiment, the thermoforming process can be carried out in a variety of ways, such as taught in "Technology of Thermoforming"; Throne, James; Hanser Publishers; 1996; pages 16-29, which are incorporated herein by reference. In some embodiments, it is a positive thermoforming process, in which gas or air pressure is applied to a softened sheet, the sheet is then stretched and pulled out like a bubble, and a male mold is introduced into the bubble from the inside. Vacuum is then applied to further stretch the part and conform the part to the male mold surface. In this thermoforming process, biaxial stretching / orientation is mainly carried out in one step when gas or air pressure is applied to the softened sheet. The molding step is then completed with a vacuum and a male mold so that the orientation is frozen in the sheet after cooling, so that the physical and appearance properties are well balanced. In other embodiments, it is a negative thermoforming process where a vacuum or physical plug is applied to the heat softened sheet and stretches and draws the sheet to near final part dimensions, and then positive air pressure from the inside or further external vacuum from the outside draws the sheet outward and conforms it to an external negative mold, freezing the orientation into the polymer upon cooling and forming the sheet into an article.

[0175] In some embodiments, the resulting bubble is further shaped, sometimes with the aid of a plunger, and thereafter the sheet is draped and shaped over a raised positive mold, and then the corners and shelf guides, etc., are pulled into the mold by applying a vacuum. In some embodiments, after removal from the mold, the molded part or article may be trimmed, punched, and chamfered as desired.

[0176] In other embodiments, thermoforming is a process in which a film or sheet of the polyester composition of the present disclosure is heated to a temperature sufficient to allow it to deform, and then the heated film or sheet is made to conform to the contours of the mold by means such as vacuum assistance, air pressure assistance, and matching mold assistance. In another embodiment, the heated film or sheet is placed in a mold and forced to conform to the mold contours, such as by applying air pressure, applying a vacuum, plunger assistance, or applying a matching mold. In some embodiments, thermoforming produces thin-walled articles.

[0177] In one embodiment, the thermoforming method molds the film or sheet into a desired shape by pressing a male mold into the heated film or sheet. In this embodiment, thermoforming involves supporting the male mold of the product between the surface or workbench equipped with vacuum. In this embodiment, the heat from an external heat source (such as a hot air blower, a heating lamp or other radiant heat source) is directed to the film or sheet. In this embodiment, the film or sheet is heated to a softening point. In this embodiment, vacuum is applied to the workbench and below the workbench and around the mold, and the heat-softened film or sheet is pulled to the workbench, so that the softened film or sheet is contacted with the mold surface. In this embodiment, the softened film or sheet is drawn into close contact with the profile of the mold surface by vacuum and consistent therewith. Thus, the film or sheet presents the shape of the mold subsequently. In this embodiment, after the film or sheet cools, it hardens and can remove the resulting product or parts from the mold.

[0178] In one embodiment, the thermoforming process comprises: forming a film or sheet from the polyester blend composition of the present disclosure; heating the film or sheet until it softens and positioning it on a mold; pulling the preheated film or sheet onto the heated mold surface; cooling the film or sheet; and subsequently removing the molded article or part from the mold cavity, or optionally, heat curing the formed film or sheet by maintaining the film or sheet in contact with the heated mold for a time sufficient to partially crystallize the film or sheet.

[0179] In one embodiment, the thermoforming method includes: forming a film or sheet from the polyester blend composition of the present disclosure; heating the film or sheet to a temperature at or above the Tg of the polyester; applying gas, vacuum and / or physical pressure to the heat softened film or sheet and stretching the film or sheet to approximately the final part size; conforming the sheet to the shape of a mold by vacuum or pressure; cooling the film or sheet to a temperature below the Tg of the polyester; and then removing the thermoformed article or part from the mold.

[0180] Films and sheets for thermoforming processes can be manufactured by any conventional method known to those skilled in the art. In one embodiment, the sheet or film is formed by extrusion. In one embodiment, the sheet or film is formed by calendaring. In one embodiment, in the thermoforming process, the film or sheet is heated to a temperature at or above the Tg of the polyester. In one embodiment, the temperature is about 10 to about 60°C higher than the Tg of the polyester. In one embodiment, the film or sheet must be heated before being placed on the thermoforming mold to achieve a shorter molding time. In one embodiment, the sheet must be heated to a temperature higher than its Tg and lower than the temperature at which the sheet sags excessively during placement on the mold cavity. In one embodiment, the molded film or sheet is allowed to cool to a temperature lower than the Tg of the polyester before being removed from the mold. In one embodiment, the thermoforming process may include vacuum assistance, air assistance, mechanical plunger assistance or matching molds. In some embodiments, the mold is heated to a temperature at or above the Tg of the film or sheet. The selection of the optimal mold temperature depends on the type of thermoforming equipment, the construction and wall thickness of the molded article, and other factors.

[0181] In some embodiments, the heated film or sheet is stretched by creating and pulling a vacuum.

[0182] In one embodiment, heat curing is the process of heat-inducing partial crystallization of a polyester film or sheet in the absence of significant orientation. In one embodiment, heat setting is achieved by maintaining the film or sheet in contact with the heated mold surface for a time sufficient to achieve a level of crystallinity that imparts adequate physical properties to the finished part. In one embodiment, the level of crystallinity should be from about 10% to about 30%.

[0183] In one embodiment, the heat-cured part can be removed from the mold cavity by known removal means. For example, in one embodiment, backblowing is used and involves breaking the vacuum established between the mold and the formed film or sheet by introducing compressed air. In some embodiments, the molded article or part is then trimmed and the waste material is ground and recycled.

[0184] In some embodiments, the addition of nucleating agents provides faster crystallization during the thermoforming process, and thus provides faster molding. In one embodiment, nucleating agents such as fine-grained inorganic or organic materials can be used. For example, in one embodiment, suitable nucleating agents include talc, titanium dioxide, calcium carbonate and immiscible or cross-linked polymers. In one embodiment, nucleating agents are used in an amount ranging from about 0.01% to about 20% based on the weight of the article. In one embodiment, other conventional additives such as pigments, dyes, plasticizers, anti-cracking agents and stabilizers can be used for thermoforming as needed. In some embodiments, anti-cracking agents improve impact strength, and nucleating agents provide faster crystallization. In some embodiments, crystallization is necessary to achieve high temperature stability.

[0185] In one embodiment, the foamed polyester film or sheet is manufactured by foaming the polyester composition of the present disclosure with a chemical and / or physical foaming agent, extruding the foamed polyester into a sheet or film, and thermoforming the foamed polyester film or sheet. Prior to foaming, additives for providing enhanced properties to the foamed polyester film may be added to the polyester. Some examples of additives include slip agents, antiblocking agents, plasticizers, optical brighteners, and ultraviolet inhibitors. In one embodiment, conventional techniques may be used to extrude or laminate the foamed polyester film on one or both sides to improve its properties. In one embodiment, a coating material may be applied to a printed surface instead of the foam film itself, which provides a product label.

[0186] The blended compositions of the present disclosure can be used as molded or formed plastic parts or as solid plastic objects. The blended compositions of the present disclosure can be used as thermoformed parts or products. The blended compositions are suitable for any application requiring transparent rigid plastics. Examples of such parts include disposable knives, forks, spoons, plates, cups, straws, and eyeglass frames, toothbrush handles, toys, car decorations, tool handles, camera parts, parts of electronic devices, razor parts, ink pen holders, disposable syringes, bottles, etc. In one embodiment, the blended compositions of the present disclosure can be used as plastics, films, fibers, and sheets. In one embodiment, the composition can be used as plastics to make bottles, bottle caps, eyeglass frames, tableware, disposable tableware, tableware handles, shelves, shelf spacers, electronic equipment housings, electronic equipment boxes, computer monitors, printers, keyboards, pipes, automotive parts, automotive interior parts, automotive decorations, signs, thermoformed letters, sidings, toys, thermally conductive plastics, eye lenses, tools, tool handles, and appliances. In another embodiment, the blended compositions of the present disclosure are suitable for use as films, sheets, fibers, molded articles, shaped articles, molded parts, shaped parts, medical devices, dental trays, dental appliances, containers, food containers, shipping containers, packaging, bottles, bottle caps, eyeglass frames, tableware, disposable tableware, tableware handles, shelves, shelf dividers, furniture components, electronic equipment housings, electronic equipment boxes, computer monitors, printers, keyboards, pipes, toothbrush handles, automotive parts, automotive interior parts, automotive trim, signs, outdoor signs, sunroofs, multilayer films, insulation parts, insulation articles, insulation Containers, thermoformed letters, siding, toys, toy parts, trays, food trays, dental trays, thermally conductive plastics, ophthalmic lenses and frames, tools, tool handles and utensils, health care products, commercial food service products, boxes, films for graphic technology applications, plastic films for plastic glass laminates, point of purchase displays, skylights, smoke vents, laminated cards, fenestrations, glass grids, dividers, ceiling tiles, lighting, machine guards, graphic arts, lenses, extruded laminated sheets or films, decorative laminates, office furniture, face masks, pharmaceutical packaging, sign supports for display shelving, and shelf price supports.

[0187] The thermoformed or thermoformable blended composition can be used to form films, molded articles, molded parts, formed articles, formed parts and sheets. The method of making the thermoformed or thermoformable blended composition into films, molded articles, molded parts, formed articles, formed parts and sheets can be according to any method known in the art. The example of molded articles includes but is not limited to: medical device packaging, pharmaceutical packaging, health care product packaging, commercial catering service products such as trays, containers, food trays, water cups, storage boxes, bottles, food processors, blenders and mixing bowls, appliances, water bottles, fresh-keeping box trays, washing machine parts, refrigerator parts, vacuum cleaner parts, eye lenses and frames, and toys.

[0188] The present disclosure further relates to articles of manufacture comprising one or more films and / or sheets comprising the polyester compositions described herein.In embodiments, the films and / or sheets of the present disclosure may have any thickness desired for the intended application.

[0189] The present disclosure further relates to one or more films and / or sheets described herein. The method of molding the polyester blend composition into one or more films and / or sheets includes any method known in the art. The example of one or more films and / or sheets disclosed includes but is not limited to one or more films and / or sheets of extrusion, one or more films and / or sheets of calendering, one or more films and / or sheets of compression molding, one or more films and / or sheets of solution casting. The method of manufacturing films and / or sheets includes but is not limited to extrusion, calendering, compression molding, wet block processing, dry block processing and solution casting.

[0190] The present disclosure further relates to molded or shaped articles as described herein. Methods for molding the polyester composition into molded or shaped articles include any methods known in the art. Examples of molded or shaped articles disclosed herein include, but are not limited to, thermoformed or thermoformable articles, injection molded articles, extrusion molded articles, injection blow molded articles, injection stretch blow molded articles, and extrusion blow molded articles. Methods for making molded articles include, but are not limited to, thermoforming, injection molding, extrusion, injection blow molding, injection stretch blow molding, and extrusion blow molding. The methods disclosed herein may include any thermoforming methods known in the art. The methods disclosed herein may include any blow molding methods known in the art, including, but not limited to, extrusion blow molding, extrusion stretch blow molding, injection blow molding, and injection stretch blow molding.

[0191] The present disclosure includes any injection blow molding manufacturing method known in the art. Although not limited thereto, a typical description of an injection blow molding (IBM) manufacturing method involves: 1) melting a composition in a reciprocating screw extruder; 2) injecting the molten composition into an injection mold to form a partially cooled tube (i.e., a preform) closed at one end; 3) moving the preform into a blow mold having a desired finished shape surrounding the preform, and closing the blow mold surrounding the preform; 4) blowing air into the preform to stretch and expand the preform to fill the mold; 5) cooling the molded product; 6) ejecting the product from the mold.

[0192] The present disclosure includes any injection stretch blow molding manufacturing method known in the art. Although not limited thereto, a typical description of an injection stretch blow molding (ISBM) manufacturing method involves: 1) melting a composition in a reciprocating screw extruder; 2) injecting the molten composition into an injection mold to form a partially cooled tube (i.e., a preform) closed at one end; 3) moving the preform into a blow mold having a desired finished shape surrounding the preform and closing the blow mold surrounding the preform; 4) stretching the preform using an internal stretch rod and blowing air into the preform to stretch and expand the preform to fill the mold; 5) cooling the molded product; 6) ejecting the product from the mold.

[0193] The present disclosure includes any extrusion blow molding manufacturing process known in the art. Although not limited thereto, a typical description of an extrusion blow molding manufacturing process involves: 1) melting a composition in an extruder; 2) extruding the molten composition through a die to form a tube (i.e., a parison) of molten polymer; 3) locking a mold having a desired finished shape around the parison; 4) blowing air into the parison to stretch and expand the extrudate to fill the mold; 5) cooling the molded article; 6) ejecting the article from the mold; and 7) removing excess plastic (commonly referred to as flash) from the article.

[0194] The following examples further illustrate how the polyesters of the present disclosure may be made and evaluated, and are intended to be illustrative only and not intended to limit the scope thereof. Unless otherwise indicated, parts are parts by weight, temperature is in degrees Celsius (Celsius) or room temperature, and pressure is at or near atmospheric. Example

[0195] Copolyester resin samples were made using the procedure described elsewhere. In all cases, the resin samples were dried prior to extrusion.

[0196] Laboratory film samples were made by extruding the resin samples into 10 mil (250 micrometer) films using a 2.5" Davis and Standard single screw extruder. These 10 mil films were cut and stretched on a Bruckner Karo 4 tenter frame at a temperature 5-15°C above the glass transition temperature (Tg) of the extruded film to a draw ratio of approximately 5:1 and to a final thickness of 50 micrometers.

[0197] Tenter film samples were made by extruding resin samples and stretching them on a commercial tenter (located at Marshall and Williams, a division of Parkinson Technologies) where the film was extruded using a 3-layer ABC die with the B layer extruded by a 2.5 inch single screw extruder and the A and C layers extruded by separate 1.25 inch single screw satellite extruders. The film was cast at a thickness of approximately 10 mils (250 microns) and then stretched at a draw ratio of 5:1 to a thickness of 50 microns. Typically, the cast thickness was 250 microns and the final film thickness was 50 microns. The line speed was 45 fpm.

[0198] The diol content of the extruded film composition is measured via NMR. All NMR spectra are recorded on a JEOL EclipsePlus 600MHz nuclear magnetic resonance spectrometer using chloroform-trifluoroacetic acid (70-30 volume / volume) for polymers or deuterated chloroform added for field lock. The acid component used in the polymer blends of the embodiments herein is 100 mole % of terephthalic acid. The total mole percent of the diol component is equal to 100 mole %, and the total mole percent of the acid component is equal to 100 mole %.

[0199] The intrinsic viscosity of the polyesters is measured herein in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / dL at 25°C and is reported in dL / g.

[0200] Shrinkage is measured herein by placing a 50 mm x 50 mm square film sample in water at a temperature between 65°C and 95°C (inclusive) with 5°C increments. The film is immersed in water for 10 seconds without restricting the shrinkage in any direction, and the shrinkage (or growth) of the film sample is measured. The percent shrinkage is calculated by the following equation: % Shrinkage = [(50 mm - length after shrinkage) / 50 mm] x 100%.

[0201] The shrinkage is measured in the direction perpendicular to the main shrinkage direction (machine direction, MD) and also in the main shrinkage direction (transverse direction, TD).

[0202] The shrinkage force of the examples herein was measured in MPa using a LabThink FST-02 Thermal Shrinkage Tester at the same temperature as used to stretch the film.

[0203] The stretched film properties of the examples herein were measured using ASTM Method D 882. The films were evaluated using multiple film stretching speeds (300 mm / min and 500 mm / min).

[0204] The glass transition temperature and strain-induced crystalline melting point (Tg and Tm, respectively) of the polyesters were determined using a TA DSC 2920 from Thermal Analyst Instruments at a scan rate of 20°C / min. Tm was measured on the first heating of the stretched sample and Tg was measured in the second heating step. In addition, the samples were crystallized in a forced air oven at 165°C for 30 minutes and then analyzed by DSC. For all samples, there was generally no crystalline melting point during the second heating of the DSC scan with a heating rate of 20°C / min.

[0205] The compatibility of materials in the recycling process has been defined in procedures published by the Association of Plastic Recyclers (APR). In the case of PETG resin, the agglomeration of PET is the main problem that has been solved by the present invention. A laboratory method was developed to simulate this industrial standard. The parameters of the laboratory agglomeration test are as follows: 582 g of PET flakes were combined with 18 g of a film of shrink sheet (the film was in its shrunk state, the film having been previously shrunk by immersion in water at 85°C for 10 seconds) (3% film to PET flakes).

[0206] • Place the PET sheet + film in an aluminum pan to a depth of 1.5 inches.

[0207] • Place the pan with the slices in a forced air oven at 208°C for 1.5 hours.

[0208] • The flakes were then carefully poured through a 0.5" sieve and the amount of flakes remaining in the pan or failing to pass through the sieve was weighed and the degree of caking (%) calculated as a percentage of the starting weight.

[0209] The Association of Plastic Recyclers (APR) has established a test for measuring whether a material is compatible with current recycling processes (Critical Guidance Protocol for Clear PET Articles with Labels and Closures PET-CG-02, revised or created on April 11, 2019). The method involves a method for measuring PET agglomeration (PET FlakeClumping Evaluation; PET-S-08; revised on November 16, 2018). The details of the test are as follows: - Grind labels (minimum 3% by weight, pre-shrunk at 85°C for 10 seconds) and bottles to 1 / 4" to 1 / 2" sheet size to produce labeled bottle sheets.

[0210] • Blend the labeled bottle flakes 50:50 with the unlabeled control bottle flakes.

[0211] • The sample was then elutriated at a setting that allowed no more than 1.2% PET to be carried on the label.

[0212] - Wash the slices with 0.3% Triton X-100 and 1.0% caustic at 88°C for 15 minutes.

[0213] • The flakes were then washed with water after all floating material was removed and then filtered to remove excess water.

[0214] • Elutriate the flakes again as before.

[0215] • For each washed sample, place 2 pounds of washed flakes (with labels) into a Teflon lined baking pan and add flakes to a layer thickness of 1.5 inches.

[0216] - Place the pan containing the flakes in a circulating oven at 208°C for 1-1 / 2 hours.

[0217] - The flakes are cooled and then passed through a screen with 0.0625 inch openings. As the material passes through the screen, no material should clump and become too large to pass through the screen.

[0218] This test is followed by extrusion / pelletization and molding steps to ensure the quality of the flakes Modulated Differential Scanning Calorimetry (MDSC) is a technique that measures the difference in heat flow between a sample and an inert reference as a function of time and temperature. Again, the same heat flux cell design as used in conventional DSC is used. However, in MDSC, different heating profiles (temperature management) are applied to the sample and the reference. Specifically, a sinusoidal modulation (oscillation) is superimposed on a conventional linear heating or cooling ramp to produce a profile in which the average sample temperature varies continuously (but not in a linear manner) with time. The net effect of applying this more complex heating profile to the sample is the same as having two experiments performed simultaneously on the material: one at a conventional linear (average) heating rate, and one at a sinusoidal (instantaneous) heating rate. The actual rates of the two simultaneous experiments depend on three operator-selectable variables: Basic heating rate (3℃ / min) Modulation cycle (60 seconds) Modulation temperature range (±1°C) The glass transition temperature and the melting peak area are analyzed using reverse heat flow. The heat of melting (Hf) during heating is measured as the integrated reverse heat flow signal. The heat of crystallization (Hc) during heating is integrated from the total heat flow signal. The relative crystallinity (C) of the sample is measured by subtracting the heat of melting (Hf) from the heat of crystallization (Hc) during heating.

[0219] Examples 1-12 Laboratory film samples were made from the resin blends and evaluated using the laboratory caking test.Details of the resin compositions and the resulting film properties derived from these compositions are described in the following examples.

[0220] Polymer blends are often used to modify the properties of resins. In these studies, it was found that blending a crystalline resin with an amorphous resin capable of forming a shrinkable film provided a new resin that can be used as a shrinkable film with an unexpectedly high strain-induced crystallization melting point, making it useful for improving the compatibility of the shrinkable film during the recycling process. Table 1 describes the composition of the three resins used to prepare these laboratory blends. Shrinkable films made with only Resin #1 or Resin #3 had acceptable shrinkable film properties, but were not designed to minimize PET agglomeration during the recycling process. Resin #2 is an example of a crystallizable copolyester resin that can be used to improve the recyclability of Resins 1 and 3. Blends made from Resins 1 and 2 or Resins 2 and 3 using an extruder produced transparent, compatible films.

[0221] Table 1 Resin# 1 2 3 PTA content (mol%) 100 100 100 EG content (mol%) 71 88 65 NPG (mol%) 27 0 0 CHDM (mol%) 0 5 23 DEG content (mol%) 3 7 12 Total amorphous monomer content (mol%) 30 12 35 .

[0222] Using a lab scale process, blends 1, 2, and 3 were prepared by combining Resin #1 and Resin #2, and Resin #2 and #3 in the combinations shown in Table 2. These blends, as well as their unblended raw materials, were converted into shrinkable films using a lab scale process, and the properties of these films were measured and summarized in Table 3. Films made with only Resin #1 or Resin #3 were not compatible with the PET recycling process and produced >1% PET agglomerates. The properties of the shrinkable films made with these blends are shown in Tables 4 and 5.

[0223] Table 2

[0224] Table 3: Measured shrink film properties Resin #1 Resin #2 Resin #3 EG content (mol%) 72 88 64 CHDM (mol%) 0 5 23 DEG content (mol%) 2 7 12 NPG (mol%) 26 0 0 Total amorphous monomer content 28 12 35 Final shrinkage (%, at 95°C) 79 36 79 MD shrinkage, at 70°C (%) -2 1 -3 Contraction force (MPa) 10.0 6 6.3 Tg (℃) 77 74 70 Strain induced crystallization melting point (℃) 180 227 155 Elongation at break (%, 300mm / min) 582 566 563 Elongation at break (%, 500mm / min) 252 598 42 PET agglomeration (%) 10.3 0.45 25 .

[0225] Table 4:

[0226] Table 5: *As indicated herein, "degree of crystallinity" is calculated as the heat of fusion minus the heat of crystallization; in those cases where this value is greater than 8; this value corresponds to a composition that is sufficiently crystalline to be recyclable under the circumstances of the present disclosure.

[0227] Examples 13-16 Tenter film samples were prepared on commercial tenter frames to produce enough material to evaluate compatibility with the recycling process using the APR test procedure. In this commercial tenter process, the resins were dried, blended, extruded into 10 mil films, and then stretched directly on the tenter frame. The resin compositions used to make these blends are described in Table 6. The blend combinations used to make these shrinkable films are shown in Table 7. The film properties of those blends are shown in Table 8.

[0228] Table 6 Resin# 4 5 6 7 8 9 10 PTA content (mol%) 100 100 100 100 100 100 100 EG content (mol%) 70 88 93 67 63 65 82 NPG (mol%) 27 0 0 0 0 0 1l CHDM (mol%) 0 5 4 23 0 23 3 DEG content (mol%) 3 7 3 10 37 12 4 Total amorphous monomer content 30 12 7 33 37 35 18 .

[0229] Table 7 Blend components Blend #13 Blend #14 Blend #15 Blend #16 Resin #10 9 15 4 47 60 40 8 15 4 6 23 36 10 5 40 7 20 10 90 100 .

[0230] Table 8

[0231] The films made with these blends have excellent shrinkable film properties and high strain-induced crystalline melting points. The strain-induced crystalline melting points of these compositions are all greater than 200°C. Typically, the strain-induced crystalline melting point must be >200°C to withstand the drying temperature of PET and remain free-flowing. The strain-induced crystalline melting points of these resin blends are much higher than the strain-induced crystalline melting points that can be produced by reactor-grade materials made with the same composition. This high strain-induced crystalline melting point is advantageous in applications where a higher melting point is required. For example, if the PET flakes are dried at a temperature above the APR test temperature (e.g., 420F or 210°C), the label will not become sticky and can still be recycled with PET. The compatibility of these films with respect to the recycling process was tested (the results are shown in Table 11). Films made with these compositions passed lower and higher drying temperatures and are therefore considered compatible with the recycling process (target <1% agglomeration is considered compatible with the recycling process).

[0232] The disclosure has been described in detail with particular reference to preferred embodiments thereof, but it will be understood that variations and modifications can be effected within the spirit and scope of the disclosure.

Claims

1. A crystallizable composition comprising a blend of polyester compositions comprising: (1) 5 to 80% of at least one crystallizable polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 30 mole % of neopentyl glycol residues; (ii) from about 0 to about less than 30 mole percent of 1,4-cyclohexanedimethanol residues; (iii) diethylene glycol residues, whether or not formed in situ; and The remainder of the diol component comprises: (iv) a residue of ethylene glycol, and (v) optionally, 0 to 20 mol %, or 0 to 10 mol %, or 0 to 5 mol % of the residue of at least one modifying diol; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %, and wherein the crystalline melting point of the crystalline polyester composition is higher than 200° C.; and (2) 20-95% of at least one amorphous polyester comprising: (a) a dicarboxylic acid component comprising: (i) from about 70 to about 100 mole percent of terephthalic acid residues; (ii) from about 0 to about 30 mole % of aromatic and / or aliphatic dicarboxylic acid residues having up to 20 carbon atoms; and (b) a diol component comprising: (i) from about 0 to about 40 mole % 2,2-dimethylpropane-1,3-diol (neopentyl glycol or NPG) residues; (ii) from about 0 to about 100 mole % 1,4-cyclohexanedimethanol (CHDM) residues; (iii) from about 0.01 to about 45 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues; (iv) from about 0 to about 40 mole % diethylene glycol (DEG) residues, whether or not formed in situ; The remainder of the diol component comprises: (v) residues of ethylene glycol, and (vi) optionally, from about 0 to about 10 mole % of the residue of at least one other modifying diol; wherein the total mole % of the dicarboxylic acid components is 100 mole %, and wherein the total mole % of the diol components is 100 mole %, and wherein the crystalline melting point of the amorphous polyester composition is below 170°C.

2. The composition of claim 1, wherein the diol component of the amorphous polyester comprises the residue of 1,4-cyclohexanedimethanol.

3. The composition of claim 1, wherein the diol component of the amorphous polyester comprises 15 to 40 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 60 to 85 mole % 1,4-cyclohexanedimethanol.

4. The composition of claim 1, wherein the diol component of the amorphous polyester comprises 20 to 40 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 60 to 80 mole % 1,4-cyclohexanedimethanol.

5. The composition of claim 1, wherein the diol component of the amorphous polyester comprises 10 to 27 mole % 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 73 to 90 mole % ethylene glycol.

6. The composition of claim 5 wherein the diol component of the amorphous polyester comprises from 70 to 100 mole percent of diacid residues of terephthalic acid, isophthalic acid, or mixtures thereof.

7. The composition of claim 1 wherein the diol component of the amorphous polyester comprises diacid residues in an amount of from 70 to 100 mole percent terephthalic acid, isophthalic acid, or esters thereof, or mixtures thereof.

8. A crystallizable film comprising any of the compositions of claims 1 to 7.

9. A stretched film comprising the film of claim 8.

10. A shrink film comprising the film of claim 8.

11. A thermoformed film or sheet comprising the composition of any one of claims 1 to 7.